Method for producing powdered granules and powdered granules

The method for producing biodegradable crosslinked resin particles through crosslinking polyhydroxyalkanoate resin with peroxide and using a peptidoglycan degrading enzyme addresses the lack of suitable biodegradable resin particles, achieving effective handling properties and environmental sustainability.

JP2025063460APending Publication Date: 2025-04-16KANEKA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023172674
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

There is no known method for producing biodegradable crosslinked resin particles, and existing methods do not yield powdered or granular forms with suitable handling properties.

Method used

A method involving the preparation of a resin particle containing polyhydroxyalkanoate resin, crosslinking with peroxide, mixing with a peptidoglycan degrading enzyme, and subsequent drying to produce powdered granules with crosslinked resin particles having a gel fraction of 50% or more and a volume average particle diameter of 0.10 μm to 10.00 μm.

Benefits of technology

The method effectively produces biodegradable crosslinked resin particles in powdered or granular form, offering excellent handling properties and contributing to environmental sustainability by addressing plastic waste issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063460000001
    Figure 2025063460000001
  • Figure 2025063460000002
    Figure 2025063460000002
  • Figure 2025063460000003
    Figure 2025063460000003
Patent Text Reader

Abstract

To provide a novel method for producing powdered granules that contain biodegradable crosslinked resin particles and offer superior handling performance.SOLUTION: Provided is a method for producing powdered granules, comprising: a preparation step of preparing an aqueous dispersion containing resin particles including a polyhydroxyalkanoate resin; a crosslinking step of decomposing a peroxide and crosslinking the resin particles; a mixing step of mixing the aqueous dispersion prepared in the crosslinking step with a peptidoglycan-degrading enzyme to form a coagulated product containing the crosslinked resin particles; and a drying step of drying the coagulated product to yield powdered granules including the crosslinked resin particles, wherein the crosslinked resin particles have a gel fraction of 50% or more and a volume-average particle diameter of 0.10 μm to 10.00 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing powder or granular material and the powder or granular material. [Background technology]

[0002] 2. Description of the Related Art Conventionally, techniques for adding various modifiers (for example, crosslinked particles) to thermoplastic resins in order to improve the mechanical strength, such as the impact strength, of thermoplastic resins have been known.

[0003] Known examples of crosslinked resin particles include crosslinked resin particles made of resins such as acrylic resins, acrylic silicone resins, and polystyrene (see, for example, Patent Documents 1 and 2).

[0004] Meanwhile, in recent years, from the viewpoint of consideration for the environment during and after the disposal of resin products, there has been active development of biodegradable resins (hereinafter, sometimes referred to as "biodegradable resins"). For example, Patent Document 3 describes crosslinking of poly(3-hydroxyalkanoate), a type of biodegradable resin, by melt-kneading the resin in the presence of an organic peroxide. However, it describes that the crosslinked resin produced by such melt-kneading is used to constitute a film and / or sheet, and there is no description at all about producing small crosslinked resin particles. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-56770 A [Patent Document 2] JP 2003-82191 A [Patent Document 3] International Publication No. 2019 / 022008 Summary of the Invention [Problem to be solved by the invention]

[0006] So far, no biodegradable crosslinked resin particles have been known. In addition, when considering the use of the crosslinked resin particles as, for example, a modifier for various thermoplastic resins, the crosslinked resin particles are preferably in the form of powder or granules. The powder or granules of the crosslinked resin particles may be required to have good handling properties.

[0007] One embodiment of the present invention has been made in consideration of the current situation, and an object of the present invention is to provide a novel method for producing a powder or granular material containing biodegradable crosslinked resin particles, the powder or granular material having excellent handleability, and the powder or granular material. [Means for solving the problem]

[0008] As a result of extensive investigations aimed at solving the above problems, the present inventors have completed one embodiment of the present invention.

[0009] That is, one embodiment of the present invention includes the following configuration. [1] A method for producing a powder or granular material, comprising: a preparation step of preparing an aqueous dispersion containing resin particles containing a polyhydroxyalkanoate resin and a peroxide; a crosslinking step of decomposing the peroxide and crosslinking the resin particles; a mixing step of mixing the aqueous dispersion obtained in the crosslinking step with a peptidoglycan degrading enzyme to obtain a coagulate containing the crosslinked resin particles; and a drying step of drying the coagulate to obtain a powder or granular material containing the crosslinked resin particles, wherein the crosslinked resin particles have a gel fraction of 50% or more and a volume average particle diameter of 0.10 μm to 10.00 μm. [2] The method for producing a powder or granular material described in [1], wherein the mixing step is a step of mixing the aqueous dispersion obtained in the crosslinking step with a peptidoglycan-degrading enzyme and further with a coagulation aid to obtain a coagulated material containing the crosslinked resin particles. [3] The method for producing powder or granular material according to [2], wherein the amount of the coagulation aid used is 0.1 to 90 parts by weight based on 100 parts by weight of the crosslinked resin particles. [4] The method for producing powder or granular material according to any one of [1] to [3], wherein the polyhydroxyalkanoate-based resin is a poly(3-hydroxyalkanoate)-based resin. [5] The method for producing powder or granular material according to any one of [1] to [4], wherein the content of the polyhydroxyalkanoate resin in 100% by weight of the resin particles is 80% by weight or more. [6] The method for producing powder or granular material according to any one of [1] to [5], wherein the crosslinked resin particles have a gel fraction of 70% to 100%. [7] The method for producing powder or granular material according to any one of [1] to [6], wherein the amount of the peroxide used is 0.01 parts by weight to 10 parts by weight based on 100 parts by weight of the resin particles. [8] The method for producing a powder or granular material according to any one of [1] to [7], wherein the preparation step is a step of preparing an aqueous dispersion containing resin particles containing the polyhydroxyalkanoate resin, the peroxide, and further a polyfunctional compound. [9] The method for producing powder or granular material according to [8], wherein the amount of the polyfunctional compound used is 0.01 to 20 parts by weight based on 100 parts by weight of the resin particles.

[10] The method for producing a powder or granular material according to any one of [1] to [9], wherein the preparation step is a step of preparing an aqueous dispersion containing resin particles containing the polyhydroxyalkanoate resin, the peroxide, and further a dispersant.

[11] The method for producing powder or granular material according to

[10] , wherein the amount of the dispersant used is 0.05 parts by weight to 10 parts by weight based on 100 parts by weight of the resin particles.

[12] A method for producing a thermoplastic resin composition, comprising a mixing step of mixing a thermoplastic resin with a powder or granule produced by the method for producing a powder or granule according to any one of [1] to

[11] .

[13] A method for producing a molded article, comprising a step of molding a resin composition produced by the method for producing a thermoplastic resin composition according to

[12] .

[14] A method for producing a compact, comprising a step of compacting a powder or granular material produced by the method for producing a powder or granular material according to any one of [1] to

[11] .

[15] A powder or granule comprising crosslinked resin particles, the crosslinked resin particles comprising a polyhydroxyalkanoate resin and a peptidoglycan-degrading enzyme, having a gel fraction of 50% or more and a volume average particle diameter of 0.10 μm to 10.00 μm. Effect of the Invention

[0010] According to one embodiment of the present invention, there is provided a method for producing a powder or granular material containing biodegradable crosslinked resin particles, which has the effect of providing a novel method for producing a powder or granular material having excellent handleability, and the powder or granular material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. In addition, embodiments or examples obtained by combining the technical means disclosed in different embodiments or examples are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical means disclosed in each embodiment. All academic documents and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and smaller than B)".

[0012] [1. Technical idea according to one embodiment of the present invention] From the viewpoint of environmental load, there is a demand for the development of biodegradable materials.

[0013] Polyhydroxyalkanoate resins (hereinafter, sometimes referred to as "PHA") are known as biodegradable resins. Polyhydroxyalkanoate resins (particularly poly(3-hydroxyalkanoate) resins) can be produced by microorganisms. For example, a PHA-producing microorganism is cultured to accumulate PHA in the cells, and then the cells in the culture medium are destroyed to separate and remove the cell components, thereby obtaining an aqueous dispersion containing PHA. Here, the aqueous dispersion containing PHA may contain peptidoglycan (hereinafter, sometimes referred to as "PG") derived from the cell components. The PG in the aqueous dispersion containing PHA can be decomposed and removed by a peptidoglycan-degrading enzyme (e.g., lysozyme).

[0014] During the study of crosslinked resin particles containing PHA, the present inventor independently discovered the following new finding: By intentionally making the PHA in the aqueous dispersion unstable by removing PG from the aqueous dispersion containing PHA, it is surprisingly possible to produce a powder containing crosslinked resin particles from the aqueous dispersion, which has excellent handleability. Based on this new finding, the present invention has been completed.

[0015] [2. Powder and granular material manufacturing method] A method for producing powder or granular material according to one embodiment of the present invention includes a preparation step of preparing an aqueous dispersion containing resin particles containing a polyhydroxyalkanoate resin and a peroxide; a crosslinking step of decomposing the peroxide and crosslinking the resin particles; a mixing step of mixing the aqueous dispersion obtained in the crosslinking step with a peptidoglycan degrading enzyme to obtain a coagulate containing the crosslinked resin particles; and a drying step of drying the coagulate to obtain powder or granular material containing the crosslinked resin particles, wherein the crosslinked resin particles have a gel fraction of 50% or more and a volume average particle diameter of 0.10 μm to 10.00 μm.

[0016] In this specification, "a method for producing powder or granular material according to one embodiment of the present invention" may be referred to as "the present production method".

[0017] Since the present production method has the above-mentioned configuration, it is possible to provide a powder containing biodegradable crosslinked resin particles and having excellent handleability.

[0018] The powder or granular material obtained by the powder or granular material manufacturing method according to one embodiment of the present invention can also be said to be a powder or granular material according to one embodiment of the present invention. In this specification, "a powder or granular material according to one embodiment of the present invention" may be referred to as "the present powder or granular material." Furthermore, the crosslinked resin particles obtained by the powder or granular material manufacturing method according to one embodiment of the present invention can also be said to be crosslinked resin particles according to one embodiment of the present invention. In this specification, "a crosslinked resin particle according to one embodiment of the present invention" may be referred to as "the present crosslinked resin particle."

[0019] In this specification, the term "powder or granule" includes both powder and granule. In this specification, the term "powder or granule" refers to an object having a median diameter of 20 μm to 10 mm. The shape of the powder or granule is not particularly limited, and may be, for example, substantially spherical, flat, cubic, spindle-shaped, needle-shaped, etc. The powder or granule is preferably in the form of a powder and / or granule, but may be in the form of a pellet as long as it is within the above-mentioned range of median diameter.

[0020] The present powder is made from resin particles containing a biodegradable resin, i.e., a polyhydroxyalkanoate-based resin, which is a biodegradable resin. Therefore, the present powder (and the present crosslinked resin particles) are biodegradable. Therefore, the present powder (and the present crosslinked resin particles) are expected to be useful as a powder (and the present crosslinked resin particles) that addresses the problem of plastic waste and is friendly to the global environment. In addition, since the present powder (and the present crosslinked resin particles) are biodegradable, a resin composition and a molded product containing the powder can suppress soil pollution and / or marine pollution due to disposal. That is, one embodiment of the present invention is expected to contribute to the achievement of the Sustainable Development Goals (SDGs), such as Goal 12 "Ensure sustainable consumption and production patterns" and / or Goal 14 "Conserve and sustainably use the oceans and marine resources for sustainable development".

[0021] In a preferred embodiment of the present invention, (i) a molded article obtained by molding a resin composition containing the powder or granule obtained by the present production method and a thermoplastic resin, or (ii) a molded article obtained by molding the powder or granule obtained by the present production method, also has the advantage of being excellent in tensile impact strength.

[0022] <Aqueous medium> The aqueous medium contained in the aqueous dispersion may be water alone or a mixed solvent of water and a water-compatible organic solvent. In the mixed solvent, the concentration of the water-compatible organic solvent is not particularly limited as long as it is equal to or lower than the solubility in water of the organic solvent used.

[0023] The organic solvent is not particularly limited, but examples thereof include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, pentanol, hexanol, and heptanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; nitriles such as acetonitrile and propionitrile; amides such as dimethylformamide and acetamide; dimethyl sulfoxide; pyridine; piperidine; and the like. Among them, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, acetonitrile, propionitrile, and the like are preferred because they are easily removed. Moreover, methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, and the like are more preferred because they are easily available. Furthermore, methanol, ethanol, and acetone are particularly preferred.

[0024] In the aqueous dispersion prepared in the preparation step, the water content in the entire aqueous medium (100% by weight) constituting the aqueous dispersion is preferably 5% by weight to 100% by weight. The water content in 100% by weight of the aqueous medium is more preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, and particularly preferably 70% by weight or more. The water content in 100% by weight of the aqueous medium may be 90% by weight or more, or may be 95% by weight or more.

[0025] In the aqueous dispersion prepared in the preparation step, the concentration of the resin particles in 100% by weight of the aqueous dispersion is not particularly limited, but may be, for example, 1% by weight to 70% by weight, or 1% by weight to 60% by weight. The concentration of the resin particles in 100% by weight of the aqueous dispersion is preferably 5% by weight to 50% by weight.

[0026] <Resin particles> The resin particles used in the present manufacturing method include a polyhydroxyalkanoate resin. The resin particles may be uncrosslinked resin particles that are not crosslinked. In this specification, the "uncrosslinked resin particles" may also be referred to as "uncrosslinked resin particles".

[0027] (PHAs) "PHA" is a general term for polymers containing hydroxyalkanoic acid as a monomer unit (monomer repeating unit), and is generally biodegradable. PHA is an aliphatic polyester, preferably a polyester not containing an aromatic ring. In this specification, "PHA" refers to a polymer containing hydroxyalkanoic acid repeating units in an amount of 50 mol% or more of all monomer repeating units (100 mol%). PHA preferably contains hydroxyalkanoic acid repeating units in an amount of 60 mol% or more, more preferably 70 mol% or more, of all monomer repeating units (100 mol%).

[0028] There is no particular limitation on the PHA. Examples of PHA include polyglycolic acid, poly(3-hydroxyalkanoate)-based resin (hereinafter sometimes referred to as "P3HA"), poly(4-hydroxyalkanoate)-based resin, and the like. As the PHA, only one type may be used alone, or two or more types may be used in combination. The PHA preferably contains a poly(3-hydroxyalkanoate)-based resin, and more preferably is a poly(3-hydroxyalkanoate)-based resin (in other words, composed only of a poly(3-hydroxyalkanoate)-based resin).

[0029] In this specification, "polyglycolic acid" refers to a compound having a repeating monomer unit of [-CH 2 The term "polyglycolic acid" refers to a resin containing 50 mol % or more of repeating units represented by the formula [-CH 2 The repeating units represented by the formula: --CO-O-- may account for 60 mol % or more, 70 mol % or more, 80 mol % or more, or 90 mol % or more of all monomer repeating units (100 mol %).

[0030] The polyglycolic acid may be a homopolymer of glycolic acid, or a copolymer of glycolic acid and a monomer other than glycolic acid (for example, a copolymer of glycolic acid and lactic acid, a copolymer of glycolic acid and caprolactone, etc.).

[0031] Polyglycolic acid can be obtained by known methods such as condensation polymerization of glycolic acid and ring-opening polymerization of glycolide.

[0032] The P3HA has the formula: [-CHR-CH 2 -CO-O-] (wherein R is C n H 2n+1where n is an integer of 1 or more and 15 or less.) is a polyhydroxyalkanoate containing the 3-hydroxyalkanoic acid repeating unit as an essential repeating unit. In this specification, "P3HA" refers to a resin containing 50 mol % or more of the 3-hydroxyalkanoic acid repeating unit out of all monomer repeating units (100 mol %). The P3HA preferably contains 60 mol % or more, and more preferably 70 mol % or more of the 3-hydroxyalkanoic acid repeating unit out of all monomer repeating units (100 mol %).

[0033] P3HA is not particularly limited, and may be a homopolymer containing the repeating unit described above, or a copolymer containing the repeating unit described above. Examples of the copolymer include copolymers of 3-hydroxybutanoic acid (hereinafter sometimes referred to as "3HB") and one or more monomers selected from the group consisting of 3-hydroxypropionic acid, 3-hydroxypentanoic acid, 3-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 3-hydroxydecanoic acid, 3-hydroxyundecanoic acid, 3-hydroxydodecanoic acid, 3-hydroxytridecanoic acid, 3-hydroxytetradecanoic acid, 3-hydroxyhexadecanoic acid, and 3-hydroxyoctadecanoic acid. Alternatively, another example of the copolymer may be, for example, a copolymer of 3HB and one or more monomers selected from the group consisting of 4-hydroxybutanoic acid, 4-hydroxypentanoic acid, 4-hydroxyhexanoic acid, 4-hydroxyheptanoic acid, 4-hydroxyoctanoic acid, 4-hydroxynonanoic acid, 4-hydroxydecanoic acid, 4-hydroxyundecanoic acid, 4-hydroxydodecanoic acid, 4-hydroxytridecanoic acid, 4-hydroxytetradecanoic acid, 4-hydroxyhexadecanoic acid, and 4-hydroxyoctadecanoic acid.

[0034] Examples of P3HA include poly(3-hydroxybutyrate) (hereinafter, sometimes referred to as "P3HB"), which is a homopolymer of 3HB, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (hereinafter, sometimes referred to as "P3HB3HH"), and poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (hereinafter, sometimes referred to as "P3HB4HB"). Only one type of P3HA may be used, or two or more types may be used in combination. In this specification, "poly(X-co-Y)" refers to a copolymer containing X repeating units and Y repeating units, and is intended to mean a copolymer obtained by copolymerizing a monomer from which the X repeating units are derived and a monomer from which the Y repeating units are derived. In addition, during the production of P3HA by a microorganism, a small amount (about 1 mol% or less) of a monomer may be copolymerized, but if it does not significantly affect the physical properties of the obtained P3HA, the monomer is considered to be not copolymerized, and the product is called by a name that does not include the monomer.

[0035] P3HA can be produced by microorganisms. Such microbially produced P3HA is usually P3HA composed only of D-form (R-form) 3-hydroxyalkanoic acid repeating units. Among the microbially produced P3HA, P3HB, P3HB3HH and P3HB4HB are preferred, and P3HB3HH and P3HB4HB are more preferred, because they are easy to produce industrially.

[0036] It is also preferred that P3HA contains a 3-hydroxybutanoic acid (3HB) repeating unit. When P3HA contains a 3HB repeating unit, the composition ratio of the 3HB repeating unit in the total monomer repeating units (100 mol%) is preferably 60 mol% to 99 mol%, more preferably 61 mol% to 97 mol%, and even more preferably 62 mol% to 95 mol%, from the viewpoint of the balance between flexibility and strength. When the composition ratio of the 3HB repeating unit in P3HA is 60 mol% or more, there is an advantage that the rigidity of the crosslinked resin particles can be further improved. On the other hand, when the composition ratio of the 3HB repeating unit in P3HA is 99 mol% or less, there is an advantage that the flexibility of the crosslinked resin particles tends to be further improved. The monomer composition ratio of P3HA can be measured by gas chromatography or the like (for example, see International Publication No. 2014 / 020838). As P3HA, two or more types having different composition ratios of the 3HB repeating unit may be used in combination.

[0037] Microorganisms that produce P3HA are not particularly limited as long as they have the ability to produce P3HA. For example, the first P3HB-producing bacterium was Bacillus megaterium, discovered in 1925, and other natural microorganisms such as Cupriavidus necator (formerly classified as Alcaligenes eutrophus and Ralstonia eutropha) and Alcaligenes latus are also known. In these microorganisms, P3HB accumulates within the bacterial cells.

[0038] Also, as producers of copolymers of 3HB and other hydroxyalkanoic acids, Aeromonas caviae, which produces P3HB3HH, and Alcaligenes eutrophus, which produces poly(3-hydroxybutyrate-co-4-hydroxybutyrate), are known. In particular, in order to increase the productivity of P3HB3HH, Alcaligenes eutrophus AC32 (FERM BP-6038) (T. Fukui, Y. Doi, J. Bateriol., 179, p4821-4830 (1997)) into which genes of P3HA synthase group have been introduced is preferred. Microorganisms that have been cultured under appropriate conditions to accumulate P3HA in the cells are used. In addition to the above, genetically modified microorganisms into which various P3HA synthesis-related genes have been introduced may be used depending on the P3HA to be produced, and culture conditions, including the type of substrate, may be optimized.

[0039] The weight average molecular weight of the PHA is not particularly limited. The weight average molecular weight of the PHA is preferably 50,000 to 3,000,000, preferably 100,000 to 2,000,000, and more preferably 150,000 to 1,500,000. When the weight average molecular weight of the PHA is 50,000 or more, it has an advantage that the tendency of the strength of the crosslinked resin particles to decrease can be reduced or avoided. Also / alternatively, when the weight average molecular weight of the PHA is 50,000 or more, it has an advantage that the tendency of the low molecular weight component to become sticky can be reduced or avoided. On the other hand, a PHA having a weight average molecular weight of 3,000,000 or less can have an advantage that the PHA is easy to manufacture and / or that the PHA is easy to handle in order to achieve the object of one embodiment of the present invention. The numerical value of the weight average molecular weight of the PHA is a value obtained by measuring the PHA before the crosslinking treatment.

[0040] The weight average molecular weight can be measured by using gel permeation chromatography (GPC) (Shimadzu Corporation's "High Performance Liquid Chromatograph 20A System"), polystyrene gel (Showa Denko KK's "KG 4A", "K-806M", etc.) as a column, and chloroform as a mobile phase. The weight average molecular weight can be determined as a molecular weight converted into polystyrene using a calibration curve obtained by measuring polystyrene with a known molecular weight by the same measurement method. In this case, the calibration curve can be created using polystyrene with weight average molecular weights of 31,400, 197,000, 668,000, and 1,920,000. As the column for the GPC, a column appropriate for measuring the molecular weight may be used.

[0041] The proportion of PHA in the resin particles is not particularly limited. The content of PHA in 100% by weight of the resin component of the resin particles may be 50% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, particularly preferably 95% by weight or more, and may be 99% by weight or more. The upper limit of the content of PHA in 100% by weight of the resin component of the resin particles is not particularly limited, and may be 100% by weight or less.

[0042] <Peroxide> The aqueous dispersion contains a peroxide. The peroxide in the aqueous dispersion can be decomposed, for example, by heating. The radicals generated by the decomposition of the peroxide act on the molecules of the resin (e.g., PHA) constituting the resin particles in the aqueous dispersion. This causes the molecular chains of the resin constituting the resin particles to directly bond with each other, thereby forming a crosslinked structure. The crosslinked resin particles obtained by this production method can be crosslinked with a peroxide.

[0043] The aqueous dispersion obtained after the crosslinking step may contain substances derived from peroxides (decomposition products of peroxides, unreacted peroxides, etc.). In addition, the powder or granule obtained by the present production method (and the present crosslinked resin particles) may have substances derived from peroxides (decomposition products of peroxides, unreacted peroxides, etc.) attached to their surfaces, etc. In other words, the powder or granule obtained by the present production method (in other words, the present powder or granule) may contain substances derived from peroxides (decomposition products of peroxides, unreacted peroxides, etc.).

[0044] The peroxide may be an organic peroxide or an inorganic peroxide. The peroxide is preferably an organic peroxide because it can increase the gel fraction more efficiently.

[0045] As the organic peroxide, it is preferable to use at least one selected from the group consisting of diacyl peroxides, alkyl peroxy esters, dialkyl peroxides, hydroperoxides, peroxyketals, peroxycarbonates, and peroxydicarbonates, taking into consideration the crosslinking temperature and / or crosslinking time in the crosslinking step.

[0046] Specific examples of such organic peroxides include butyl peroxy neododecanoate, octanoyl peroxide, dilauroyl peroxide, succinic peroxide, a mixture of toluoyl peroxide and benzoyl peroxide, benzoyl peroxide, bis(butylperoxy)trimethylcyclohexane, butylperoxylaurate, dimethyldi(benzoylperoxy)hexane, bis(butylperoxy)methylcyclohexane, bis(butylperoxy)cyclohexane, and butylperoxybenzo. ester, butyl bis(butylperoxy)valerate, dicumyl peroxide, di-t-hexyl peroxide, t-butylperoxy 2-ethylhexanoate, t-butylperoxyisobutyrate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxymethyl monocarbonate, t-pentylperoxymethyl monocarbonate, t-hexylperoxymethyl monocarbonate, t-heptylperoxymethyl monocarbonate, t-octylperoxymethyl monocarbonate, 1 ,1,3,3-tetramethylbutylperoxymethyl monocarbonate, t-butylperoxyethyl monocarbonate, t-pentylperoxyethyl monocarbonate, t-hexylperoxyethyl monocarbonate, t-heptylperoxyethyl monocarbonate, t-octylperoxyethyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyethyl monocarbonate, t-butylperoxy n-propyl monocarbonate, t-pentylperoxy n-propyl monocarbonate, t-hexylperoxyethyl monocarbonate peroxy n-propyl monocarbonate, t-heptyl peroxy n-propyl monocarbonate, t-octyl peroxy n-propyl monocarbonate, 1,1,3,3-tetramethylbutyl peroxy n-propyl monocarbonate, t-butyl peroxy isopropyl monocarbonate, t-pentyl peroxy isopropyl monocarbonate, t-hexyl peroxy isopropyl monocarbonate, t-heptyl peroxy isopropyl monocarbonate, t-octyl peroxy isopropyl monocarbonate, 1,1,3,3-Tetramethylbutylperoxyisopropyl monocarbonate, t-butylperoxyn-butyl monocarbonate, t-pentylperoxyn-butyl monocarbonate, t-hexylperoxyn-butyl monocarbonate, t-heptylperoxyn-butyl monocarbonate, t-octylperoxyn-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyn-butyl monocarbonate, t-butylperoxyisobutyl monocarbonate, t-pentylperoxyisobutyl monocarbonate, t -Hexylperoxyisobutylmonocarbonate, t-heptylperoxyisobutylmonocarbonate, t-octylperoxyisobutylmonocarbonate, 1,1,3,3-tetramethylbutylperoxyisobutylmonocarbonate, t-butylperoxysec-butylmonocarbonate, t-pentylperoxysec-butylmonocarbonate, t-hexylperoxysec-butylmonocarbonate, t-heptylperoxysec-butylmonocarbonate, t-octylperoxysec-butylmonocarbonate peroxy t-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy sec-butyl monocarbonate, t-butylperoxy t-butyl monocarbonate, t-pentylperoxy t-butyl monocarbonate, t-hexylperoxy t-butyl monocarbonate, t-heptylperoxy t-butyl monocarbonate, t-octylperoxy t-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy t-butyl monocarbonate, t-butylperoxy 2-ethylhexyl monocarbonate, t-pentylperoxy 2-ethylhexyl monocarbonate, ethylhexyl monocarbonate, t-hexylperoxy 2-ethylhexyl monocarbonate, t-heptylperoxy 2-ethylhexyl monocarbonate, t-octylperoxy 2-ethylhexyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexyl monocarbonate, diisobutyl peroxide, cumylperoxy neodecanoate, di-n-propylperoxydicarbonate, diisopropylperoxydicarbonate, di-sec-butylperoxydicarbonate, 1,1,3,3-Tetramethylbutylperoxyneodecanoate, bis(4-t-butylcyclohexyl)peroxydicarbonate, bis(2-ethylhexyl)peroxydicarbonate, t-hexylperoxyneodecanoate, t-butylperoxyneodecanoate, t-butylperoxyneoheptanoate, t-hexylperoxypivalate, t-butylperoxypivalate, di(3,5,5-trimethylhexanoyl)peroxide, dilauroyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, disuccinic acid peroxide, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy) Examples of organic peroxides include hexane, t-hexylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoylperoxide, t-butylperoxy-2-ethylhexylcarbonate, t-butylperoxyisopropylcarbonate, 1,6-bis(t-butylperoxycarbonyloxy)hexane, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyacetate, t-butylperoxybenzoate, t-amylperoxy, 3,5,5-trimethylhexanoate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, and 2,2-di-t-butylperoxybutane. The organic peroxides may be used alone or in combination of two or more.

[0047] Among these, t-butylperoxyisopropyl monocarbonate, t-pentylperoxyisopropyl monocarbonate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxy2-ethylhexyl monocarbonate, t-pentylperoxy2-ethylhexyl monocarbonate, t-hexylperoxy2-ethylhexyl monocarbonate, t-amylperoxyisopropyl monocarbonate, di-t-hexyl peroxide, t-butylperoxy2-ethylhexanoate, Preferred organic peroxides are t-butyl peroxyisobutyrate, t-hexylperoxy 2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexanoate, t-butyl peroxypivalate, t-hexyl peroxypivalate, t-butyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, and 1,1,3,3-tetramethylbutylperoxyneodecanoate, because they can efficiently promote crosslinking of the resin that constitutes the resin particles.

[0048] Since the crosslinking temperature in the crosslinking step can be set low, the peroxide is preferably a compound exhibiting a one-hour half-life temperature of 200° C. or less, more preferably a compound exhibiting a one-hour half-life temperature of 170° C. or less, and even more preferably a compound exhibiting a one-hour half-life temperature of 140° C. or less. The lower limit of the one-hour half-life temperature of the peroxide may be 50° C. or more, 60° C. or more, or 70° C. or more.

[0049] Particularly preferred organic peroxides exhibiting such a one-hour half-life temperature are t-butylperoxyisopropylmonocarbonate, t-butylperoxy2-ethylhexylmonocarbonate, di-sec-butylperoxydicarbonate, t-butylperoxy2-ethylhexanoate, t-butylperoxyisobutyrate, t-hexylperoxy2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy2-ethylhexanoate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxyneodecanoate, t-hexylperoxyneodecanoate, and 1,1,3,3-tetramethylbutylperoxyneodecanoate.

[0050] The case where the peroxide is an inorganic peroxide will be described. Examples of the inorganic peroxide include hydrogen peroxide, potassium peroxide, calcium peroxide, sodium peroxide, magnesium peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate, taking into consideration the crosslinking temperature and / or crosslinking time in the crosslinking step. Among them, hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate are preferred in terms of ease of handling and having a decomposition temperature suitable for the crosslinking temperature in the crosslinking step. The inorganic peroxide may be used alone or in combination of two or more. An organic peroxide and an inorganic peroxide may be used in combination.

[0051] <Coagulation aid> The mixing step is preferably a step of mixing the aqueous dispersion obtained in the crosslinking step with a peptidoglycan degrading enzyme and further with a coagulation aid to obtain a coagulated product containing the crosslinked resin particles. In other words, the aqueous dispersion prepared in the preparation step preferably contains a coagulation aid. In this specification, the term "coagulation aid" refers to a substance that can suppress the stickiness of the crosslinked resin particles. When the aqueous dispersion prepared in the preparation step contains a coagulation aid, the resulting powder has the advantage of being easier to handle.

[0052] The coagulation aid is not particularly limited as long as it is a substance that has the function of suppressing stickiness of the crosslinked resin particles, and may be either an inorganic component or an organic component.

[0053] As the inorganic component usable as the coagulation aid, a component known as an inorganic filler for thermoplastic resins can be used. As the inorganic component usable as the coagulation aid, for example, silica-based inorganic filler (for example, quartz, fumed silica, silicic anhydride, fused silica, crystalline silica, amorphous silica, filler obtained by condensing alkoxysilane, ultrafine powder amorphous silica, etc.), alumina, zircon, iron oxide, zinc oxide, titanium oxide, silicon nitride, boron nitride, aluminum nitride, silicon carbide, glass, silicone rubber, silicone resin, titanium oxide, carbon fiber, mica, graphite, carbon black, ferrite, graphite, diatomaceous earth, white clay, clay, talc, calcium carbonate, manganese carbonate, magnesium carbonate, barium sulfate, silver powder, etc. can be mentioned. These inorganic components may be surface-treated. In addition, these inorganic components may be used alone or in combination of two or more.

[0054] The inorganic component may be mixed in its solid form with the aqueous dispersion obtained in the crosslinking step, or the aqueous dispersion of the inorganic component may be prepared and then mixed with the aqueous dispersion obtained in the crosslinking step.

[0055] The method for preparing the aqueous dispersion of the inorganic component is not particularly limited. For example, after mixing water and the inorganic component, the mixture obtained is subjected to shearing using a homogenizer or the like, and the inorganic component is finely divided and dispersed in water, thereby obtaining an aqueous dispersion of the inorganic component. When preparing the aqueous dispersion of the inorganic component, temperature adjustment, pH adjustment, etc. may be appropriately performed. A commercially available aqueous dispersion of the inorganic component may be used.

[0056] The aqueous dispersion of the inorganic component may contain a dispersant to improve the dispersion stability of the inorganic component. The dispersant will be described later. The dispersant described later may be used alone or in combination of two or more.

[0057] The case where the aqueous dispersion of the inorganic component contains a dispersant will be described. The content of the dispersant in the aqueous dispersion of the inorganic component is not particularly limited. The content of the dispersant in the aqueous dispersion of the inorganic component is, for example, preferably 0.05 parts by weight to 10 parts by weight, more preferably 0.1 parts by weight to 5 parts by weight, and particularly preferably 0.15 parts by weight to 3 parts by weight, relative to 100 parts by weight of the inorganic component.

[0058] The organic compound that can be used as the coagulation aid is not particularly limited, but it is preferable that the organic compound is water-soluble because it is easy to handle.

[0059] Specific examples of organic compounds that can be used as the coagulation aid include, but are not limited to, thermoplastic resins, polyhydric alcohols, fatty acid amides, polysaccharides, oligosaccharides, and glycerin fatty acid esters.

[0060] (thermoplastic resin) The thermoplastic resin is not particularly limited, but examples thereof include polyolefin resins such as polyethylene and polypropylene, acrylic resins such as polyvinyl chloride, polystyrene, polyvinyl acetate, polyurethane, polytetrafluoroethylene, and polymethyl methacrylic acid, AS resins, polyamides, polyacetals, polycarbonates, modified polyphenylene ethers, polyester resins, and cyclic polyolefins. Only one of these thermoplastic resins may be used, or two or more may be used in combination. The thermoplastic resin preferably has a gel fraction of less than 50%. The thermoplastic resin is preferably not crosslinked.

[0061] As the thermoplastic resin, polyester-based resin is particularly preferred. Examples of the polyester-based resin include aliphatic polyester and aliphatic aromatic polyester. Examples of the aliphatic polyester include (i) PHA, (ii) polycaprolactone (PCL), (iii) polylactic acid (PLA), and (iv) aliphatic polyester having a structure in which aliphatic diol and aliphatic dicarboxylic acid are polycondensed.

[0062] Specific examples of PHA are the same as those explained in the section (PHA) above, so the explanation is incorporated herein by reference and will not be repeated here.

[0063] As the polylactic acid, a conventionally known polylactic acid can be used. The polylactic acid may be crystalline polylactic acid, amorphous polylactic acid, or a mixture of crystalline polylactic acid and amorphous polylactic acid.

[0064] The polylactic acid may be a homopolymer of lactic acid, a copolymer of lactic acid and other monomers, or a blend of a homopolymer of lactic acid and a copolymer of lactic acid and other monomers.

[0065] Examples of the other monomers include aliphatic hydroxycarboxylic acids other than lactic acid, aliphatic polyhydric alcohols, aliphatic polycarboxylic acids, and polyfunctional polysaccharides.

[0066] The lactic acid raw material for producing polylactic acid is not particularly limited, and L-lactic acid, D-lactic acid, DL-lactic acid, or a mixture thereof, or L-lactide, D-lactide, meso-lactide, or a mixture thereof, etc. Lactic acid obtained by microbial fermentation from renewable raw materials derived from plants such as starch can be suitably used.

[0067] The method for producing polylactic acid is not particularly limited, and known methods such as dehydration condensation polymerization and ring-opening polymerization can be used.

[0068] The weight-average molecular weight of polylactic acid is not particularly limited, but is preferably 50,000 to 1,000,000, more preferably 70,000 to 700,000, and even more preferably 100,000 to 400,000. When the weight-average molecular weight of polylactic acid is 50,000 or more, sufficient rigidity and / or strength can be obtained in the present resin composition and its molded article. On the other hand, polylactic acid having a weight-average molecular weight of 1,000,000 or less can have the advantage that the polylactic acid is easy to produce and / or easy to handle in order to achieve the object of one embodiment of the present invention.

[0069] Specific examples of aliphatic polyesters having a structure formed by polycondensation of an aliphatic diol and an aliphatic dicarboxylic acid include polyethylene succinate, polybutylene succinate (hereinafter sometimes referred to as "PBS"), polyhexamethylene succinate, polyethylene adipate, polybutylene adipate, polyhexamethylene adipate, polybutylene succinate adipate (hereinafter sometimes referred to as "PBSA"), polyethylene sebacate, polybutylene sebacate, and the like.

[0070] The aliphatic aromatic polyester includes an aliphatic aromatic polyester (both an aliphatic compound and an aromatic compound are monomers) obtained by copolymerizing both an aliphatic compound and an aromatic compound as monomers. Examples of the aliphatic aromatic polyester include polybutylene adipate terephthalate (hereinafter sometimes referred to as "PBAT"), polybutylene sebacate terephthalate (hereinafter sometimes referred to as "PBSeT"), polybutylene azelate terephthalate (hereinafter sometimes referred to as "PBAzT"), polybutylene succinate terephthalate (hereinafter sometimes referred to as "PBST"), and polybutylene succinate adipate terephthalate (hereinafter sometimes referred to as "PBSAT").

[0071] Examples of polyhydric alcohols include ethylene glycol, propylene glycol, diethylene glycol, glycerin, trimethylolpropane, trimethylolethane, 1,2,6-hexanetriol, erythritol, pentaerythritol, threitol, arabinitol, xylitol, ribitol, iditol, galactitol, glucitol, mannitol, sorbitol, inositol, maltotol, lactitol, etc. Among these, sugar alcohols are preferred, and pentaerythritol is particularly preferred.

[0072] Examples of fatty acid amides include behenamide, erucamide, uric acid amide, coconut acid amide, stearamide, palmitic acid amide, behenamide, brassidic acid amide, acetamide, benzamide, propionic acid amide, oleic acid amide, ricinoleic acid amide, etc. Among these, behenamide and / or erucamide are preferred.

[0073] Examples of polysaccharides include chitin, chitosan, starch, cellulose, agarose, carrageenan, heparin, hyaluronic acid, alginic acid, pectin, xyloglucan, glucomannan, glycogen, dextran, cellulose, and cellulose derivatives such as acetylcellulose and methylcellulose.

[0074] Examples of oligosaccharides include fructooligosaccharides, soybean oligosaccharides, galactooligosaccharides, xylooligosaccharides, isomaltooligosaccharides, lactose-fructose oligosaccharides, and cyclic oligosaccharides such as cyclodextrin and cycloisomaltooligosaccharide.

[0075] Examples of glycerin fatty acid esters include monoglycerides, acetylated monoglycerides, organic acid monoglycerides, polyglycerin fatty acid esters, and the like.

[0076] The above-mentioned organic components (for example, organic compounds) may be used alone or in combination of two or more.

[0077] The organic component (e.g., organic compound) may be mixed in the form of a solid (e.g., powder) with the aqueous dispersion obtained in the crosslinking step. The organic component may be mixed with the aqueous dispersion obtained in the crosslinking step after preparing an aqueous dispersion of the organic component.

[0078] The method for preparing the aqueous dispersion of an organic component (e.g., an organic compound) is not particularly limited. For example, after mixing water and an organic component, the resulting mixture is stirred, temperature adjusted, and / or pH adjusted to obtain an aqueous dispersion of the organic component. A commercially available aqueous dispersion of an organic component may be used.

[0079] The aqueous dispersion of an organic component (e.g., an organic compound) may contain a dispersant to improve the stability of the dispersion of the organic component. The dispersant will be described later. The dispersant described later may be used alone or in combination of two or more.

[0080] The case where the aqueous dispersion of an organic component (e.g., an organic compound) contains a dispersant will be described. The content of the dispersant in the aqueous dispersion of the organic component is not particularly limited. The content of the dispersant in the aqueous dispersion of the organic component is, for example, preferably 0.05 parts by weight to 10 parts by weight, more preferably 0.1 parts by weight to 5 parts by weight, and particularly preferably 0.15 parts by weight to 3 parts by weight, relative to 100 parts by weight of the organic component.

[0081] The amount of the coagulation aid used in the present production method (e.g., the mixing step) is preferably 0.1 to 90 parts by weight, more preferably 0.2 to 85 parts by weight, even more preferably 0.3 to 80 parts by weight, and particularly preferably 0.4 to 75 parts by weight, relative to 100 parts by weight of the crosslinked resin particles. This configuration has the advantage that a powder or granule with even better handleability can be obtained.

[0082] <Polyfunctional compounds> The preparation step is preferably a step of preparing an aqueous dispersion containing resin particles containing the polyhydroxyalkanoate resin, the peroxide, and further a polyfunctional compound. In other words, the aqueous dispersion prepared in the preparation step preferably contains a peroxide and a polyfunctional compound. When both a peroxide and a polyfunctional compound are used for crosslinking the resin particles, it is possible to increase the gel fraction of the crosslinked resin particles with a smaller amount of peroxide compared to the case where only a peroxide is used. In other words, the powder particles (and the present crosslinked resin particles) obtained by the present production method are preferably crosslinked in the presence of a peroxide and a polyfunctional compound.

[0083] The polyfunctional compound refers to a compound having two or more functional groups (e.g., radical reactive groups) in one molecule that can crosslink the resin (e.g., PHA) that constitutes the resin particles. The polyfunctional compound is not particularly limited, but is preferably a compound that is reactive with a radical generated from a peroxide, and is particularly preferably a compound having two or more radical reactive groups in one molecule. The radical reactive group is preferably at least one selected from the group consisting of a vinyl group, an allyl group, an acryloyl group, and a methacryloyl group.

[0084] Such polyfunctional compounds are not particularly limited, but examples thereof include allyl (meth)acrylate, allyl alkyl (meth)acrylates, allyloxy alkyl (meth)acrylates, polyfunctional (meth)acrylates having two or more (meth)acrylic groups, such as ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate, divinylbenzene, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, and divinylbenzene. Preferably, the compound is one or more selected from the group consisting of allyl methacrylate, triallyl isocyanurate, butanediol di(meth)acrylate, and divinylbenzene, and more preferably, the compound is one or more selected from the group consisting of allyl methacrylate and triallyl isocyanurate.

[0085] When a crosslinked structure is formed in the presence of a polyfunctional compound, the resulting crosslinked resin particles may usually contain a structure derived from the polyfunctional compound, in which case the molecular chains of the resin constituting the resin particles are bonded to each other via the structure derived from the polyfunctional compound.

[0086] <Dispersant> The preparation step is preferably a step of preparing an aqueous dispersion containing resin particles containing the polyhydroxyalkanoate resin, the peroxide, and a dispersant. In other words, the aqueous dispersion prepared in the preparation step preferably further contains a dispersant. By including a dispersant in the aqueous dispersion prepared in the preparation step, the dispersibility of the resin particles in the aqueous dispersion can be increased, and the crosslinking reaction can proceed uniformly.

[0087] Examples of dispersants include anionic surfactants such as sodium dioctyl sulfosuccinate, sodium dodecyl sulfate, sodium lauryl sulfate, and sodium oleate; cationic surfactants such as lauryl trimethyl ammonium chloride; nonionic surfactants such as glycerin fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, and polyoxyethylene polyoxypropylene glycol; and water-soluble polymers such as polyvinyl alcohol, ethylene-modified polyvinyl alcohol, polyvinylpyrrolidone, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, polyacrylic acid, sodium polyacrylate, potassium polyacrylate, polymethacrylic acid, and sodium polymethacrylate. Only one of these dispersants may be used, or two or more of them may be used in combination.

[0088] When a dispersant is used in the preparation step, the amount of the dispersant used is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and particularly preferably 0.15 to 3 parts by weight, relative to 100 parts by weight of the resin particles. The amount of the dispersant used may be 2 parts by weight or less, 1 part by weight or less, or 0.5 parts by weight or less, relative to 100 parts by weight of the resin particles.

[0089] Some dispersants may inactivate the enzymatic activity of the peptidoglycan degrading enzyme. As the dispersant, a dispersant that has no risk of inactivating the enzymatic activity of the peptidoglycan degrading enzyme or that has little effect on the enzymatic activity is preferred. In addition, when a dispersant that can inactivate the enzymatic activity of the peptidoglycan degrading enzyme is used, it is preferred that the amount of the dispersant used is small.

[0090] <Foaming agent> The present crosslinked resin particles are different from the expanded resin particles disclosed in WO 2007 / 049694 and WO 2019 / 146555, and are preferably not expanded. In other words, the present crosslinked resin particles are preferably those that do not substantially contain air bubbles inside the particles. "Substantially does not contain air bubbles inside the particles" means that the volume of air bubbles (spaces) is 10% or less in 100% of the volume of the crosslinked resin particles. In the present manufacturing method, it is preferable not to use a foaming agent. The aqueous dispersion prepared in the preparation step preferably does not contain a foaming agent. "The aqueous dispersion does not contain a foaming agent" means that the content of the foaming agent in the aqueous dispersion is 1.8 parts by weight or less relative to 100 parts by weight of the resin component constituting the resin particles.

[0091] (Other additives) The aqueous dispersion prepared in the preparation step may further contain other additives in addition to the above-mentioned components, such as antioxidants, hydrolysis inhibitors, antiblocking agents, crystal nucleating agents, lubricants, and ultraviolet absorbers.

[0092] <Preparation process> The preparation step is not particularly limited as long as it is a step of preparing an aqueous dispersion containing resin particles containing a polyhydroxyalkanoate-based resin and a peroxide.

[0093] The preparation step may include, for example, a step of preparing a mixture containing an aqueous medium and resin particles (hereinafter, sometimes referred to as an "aqueous dispersion precursor"), and a step of adding a peroxide to the mixture (aqueous dispersion precursor).

[0094] Alternatively, the preparation step may include a step of preparing a mixture containing an aqueous medium and a peroxide, and a step of adding a mixture containing an aqueous medium and resin particles (aqueous dispersion precursor) to the mixture.

[0095] The process for preparing the aqueous dispersion precursor containing an aqueous medium and resin particles is not particularly limited. The case where the resin particles are composed only of a resin (e.g., PHA) produced in the body of a microorganism will be described. In this case, the process for preparing the aqueous dispersion precursor may include, for example, a process for culturing a resin-producing microorganism (e.g., PHA-producing microorganism) to accumulate the resin in the bacterial body, and then destroying the bacterial body in the culture liquid to separate and remove the bacterial body components to obtain an aqueous dispersion precursor. The aqueous dispersion precursor obtained by this process may be further concentrated or diluted. According to this process, the process from producing the resin particles by culturing the resin-producing microorganism to the crosslinking process can be carried out without separating the resin particles from water.

[0096] The step of preparing the aqueous dispersion precursor containing the aqueous medium and the resin particles may be, for example, a step of dispersing dried resin particles (e.g., powder particles) in an aqueous medium such as water to obtain the aqueous dispersion precursor. The aqueous medium may contain, in addition to water, the above-mentioned organic solvent compatible with water.

[0097] The volume average particle diameter of the resin particles is preferably within the same range as the volume average particle diameter of the crosslinked resin particles described above.When the resin particles produced by PHA-producing microorganisms are used as raw materials, the volume average particle diameter of the resin particles can usually be within the above range.Therefore, when the resin particles produced by PHA-producing microorganisms are used as raw materials, the aqueous dispersion of resin particles having a desired volume average particle diameter can be obtained without carrying out a special process for adjusting particle diameter.

[0098] In the step of adding the peroxide, the peroxide may be any of those described above. In the step of adding the peroxide, the peroxide may be added in various forms, such as solid or liquid. In addition, in this step, a liquid peroxide diluted with a diluent or the like may be added. In addition, in this step, the total amount of the peroxide used may be added all at once, or may be added continuously or in portions. In addition, during the progress of the crosslinking step described below, a polyfunctionalized product may be further added. In this case, the total amount of the polyfunctionalized product used may be added all at once, or may be added continuously or in portions.

[0099] The amount of peroxide used in this production method is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 8 parts by weight, even more preferably 0.3 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, per 100 parts by weight of resin particles.

[0100] According to a manufacturing method in which resin particles are crosslinked in an aqueous dispersion using a peroxide, crosslinking can be promoted while maintaining the particle size (volume) before crosslinking, and crosslinked resin particles can be easily obtained. On the other hand, in a method in which a resin is crosslinked by melt kneading in the presence of a peroxide, this can be difficult to achieve.

[0101] In addition, the manufacturing method in which resin particles are crosslinked in an aqueous dispersion using a peroxide makes it easy to control the temperature increase caused by the heat generated during the crosslinking reaction, and is advantageous in efficiently obtaining crosslinked resin particles having a safe and stable crosslinked structure (quality).

[0102] The present manufacturing method preferably further includes an addition step of adding a polyfunctional compound to the aqueous dispersion. In other words, the preparation step in the present manufacturing method preferably further includes an addition step of adding a polyfunctional compound to the aqueous dispersion. The polyfunctional compound may be any of the above-mentioned compounds. In the addition step, the polyfunctional compound may be added in various forms such as solid and liquid. In addition, in the addition step, a liquid diluted with a diluent or the like may be added. In addition, in the addition step, the entire amount of the polyfunctional compound used may be added all at once, or may be added continuously or in portions. In addition, during the progress of the crosslinking step described below, the polyfunctionalized material may be further added. In that case, the entire amount of the polyfunctionalized material used may be added all at once, or may be added continuously or in portions.

[0103] The timing of performing the addition step of adding the polyfunctional compound to the aqueous dispersion (in other words, the timing of adding the polyfunctional compound to the aqueous dispersion) is not particularly limited. The addition step may be performed simultaneously with the step of adding the peroxide to the aqueous dispersion precursor. For example, after preparing an aqueous dispersion precursor containing an aqueous medium and resin particles, the peroxide and the polyfunctional compound may be added to the obtained aqueous dispersion precursor. The peroxide and the polyfunctional compound may be added simultaneously (together) or separately. After preparing a mixture containing the peroxide and the polyfunctional compound, the mixture may be added to the aqueous dispersion precursor.

[0104] Alternatively, the addition step may be performed between the step of preparing an aqueous dispersion precursor containing an aqueous medium and resin particles and the step of adding a peroxide to the aqueous dispersion precursor. For example, after preparing an aqueous dispersion precursor containing an aqueous medium and resin particles, a polyfunctional compound may be added to the obtained aqueous dispersion precursor, and then a peroxide may be added to the aqueous dispersion precursor containing an aqueous medium, resin particles, and a polyfunctional compound. Alternatively, the addition step may be performed after the step of adding a peroxide to the aqueous dispersion precursor. For example, after preparing an aqueous dispersion containing an aqueous medium, resin particles, and a peroxide, a polyfunctional compound may be added to the obtained aqueous dispersion.

[0105] In this manufacturing method, the amount of the polyfunctional compound used is preferably 0.01 to 20 parts by weight, more preferably 0.05 to 15 parts by weight, even more preferably 0.1 to 10 parts by weight, even more preferably 0.2 to 5 parts by weight, and particularly preferably 0.3 to 3 parts by weight, relative to 100 parts by weight of the resin particles.

[0106] <Impregnation process> The present manufacturing method preferably includes an impregnation step of impregnating the resin particles with a peroxide after the preparation step and before the crosslinking step. When a polyfunctional compound is used in the preparation step, the impregnation step is preferably a step in which the resin particles can be impregnated with the polyfunctional compound in addition to the crosslinking agent, and more preferably a step in which the peroxide and the polyfunctional compound can be impregnated. In the impregnation step, the peroxide and / or the polyfunctional compound are preferably at least partially impregnated into the resin particles, and more preferably completely impregnated.

[0107] An example of the impregnation step is a step of setting (heating) the temperature of the aqueous dispersion to a predetermined temperature (impregnation temperature) while a peroxide and, optionally, a polyfunctional compound are being added to an aqueous dispersion precursor containing resin particles, and / or after the peroxide and, optionally, a polyfunctional compound are being added, and further, optionally, maintaining the temperature of the aqueous dispersion at the predetermined temperature (impregnation temperature) for a predetermined time (impregnation time).

[0108] In the impregnation step, the set temperature (heating temperature) of the aqueous dispersion, i.e., the impregnation temperature, is not particularly limited. The impregnation temperature may be, for example, (i) 0°C or higher and lower than a temperature suitable for decomposing the peroxide used in the crosslinking step described later, (ii) 0°C or higher and lower than 80°C, or (iii) 0°C or higher and lower than 60°C.

[0109] In the impregnation step, the time for which the aqueous dispersion is held at the impregnation temperature, i.e., the impregnation time, is not particularly limited. The impregnation time may be, for example, 1 minute to 5 hours, 10 minutes to 3 hours, or 30 minutes to 1 hour.

[0110] In the impregnation step, the aqueous dispersion is maintained at the impregnation temperature and for the impregnation time described above, whereby the resin particles can be impregnated with the peroxide and, if used, the polyfunctional compound.

[0111] <Crosslinking process> This manufacturing method includes a crosslinking step of decomposing the peroxide and crosslinking the resin particles. As described above, the decomposition of the peroxide generates radicals, and the radicals directly bond the molecular chains of the resin constituting the resin particles, that is, a crosslinked structure can be formed. It can be said that the resin particles are crosslinked as long as the peroxide is decomposed. Therefore, the crosslinking step is not particularly limited as long as it can decompose the peroxide.

[0112] The crosslinking step may be, for example, a step of heating the aqueous dispersion obtained in the preparation step or the aqueous dispersion obtained through the preparation step and the impregnation step to a temperature suitable for decomposition of peroxide (hereinafter, also referred to as the "crosslinking temperature"). Alternatively, the crosslinking step may be a step of mixing the aqueous dispersion obtained in the preparation step or the aqueous dispersion obtained through the preparation step and the impregnation step with a substance that promotes decomposition of peroxide (for example, an acid, an alkali, a reducing agent, etc.).

[0113] The aqueous dispersion obtained in the preparation step, and the aqueous dispersion obtained through the preparation step and the impregnation step, may each independently be an aqueous dispersion such as the following: (i) an aqueous dispersion comprising resin particles impregnated with peroxide and, optionally, peroxide that is not impregnated into the resin particles; (ii) an aqueous dispersion containing resin particles partially impregnated with peroxide and peroxide that is not impregnated into the resin particles; (iii) an aqueous dispersion containing resin particles not impregnated with peroxide and peroxide not impregnated into the resin particles; (iv) an aqueous dispersion containing resin particles partially impregnated with peroxide, resin particles not impregnated with peroxide, and peroxide not impregnated into the resin particles; or (v) An aqueous dispersion containing resin particles impregnated with peroxide and resin particles partially impregnated with peroxide and / or resin particles not impregnated with peroxide and peroxide not impregnated into the resin particles.

[0114] The crosslinking temperature is preferably within a range of about 25°C above and below the one-hour half-life temperature of the peroxide (one-hour half-life temperature -25°C to one-hour half-life temperature +25°C). Specifically, the crosslinking temperature is preferably 30°C to 140°C, more preferably 50°C to 135°C, and even more preferably 60°C to 130°C. According to this configuration, it is possible to crosslink the uncrosslinked resin particles at a temperature lower than the melting temperature of the resin component constituting the uncrosslinked resin particles, so that deterioration of the uncrosslinked resin particles due to heat can be avoided. The melting temperature of PHA is, for example, 50°C to 210°C.

[0115] In the crosslinking step, the aqueous dispersion is preferably maintained at the above-mentioned crosslinking temperature for a predetermined time (crosslinking time). The crosslinking time is not particularly limited, but is preferably 1 minute to 15 hours, and more preferably 1 hour to 10 hours. This configuration allows the crosslinking reaction using the peroxide to proceed sufficiently.

[0116] In the crosslinking step, the pH of the aqueous dispersion is preferably 4 to 13, more preferably 7 to 12. When the pH of the aqueous dispersion is within the above range, there is an advantage that the dispersibility of the crosslinked resin particles in the aqueous dispersion is good.

[0117] In the crosslinking step, the pressure in the reactor is preferably less than 1 MPa in gauge pressure, more preferably less than 0.8 MPa, even more preferably less than 0.6 MPa, and particularly preferably less than 0.2 MPa. The pressure in the reactor is preferably 0 MPa or more in gauge pressure. When the pressure in the reactor is within the above range, the reaction can be carried out under mild conditions, which has the advantage of increasing the options for reaction vessels.

[0118] In the crosslinking step, it is sufficient that at least a portion of the resin particles is crosslinked. In the crosslinking step, it is preferable that the resin particles are crosslinked to such an extent that crosslinked resin particles having a desired gel fraction (for example, 50% or more) are obtained.

[0119] <Mixing process> In the mixing step, the aqueous dispersion is mixed with a peptidoglycan degrading enzyme, and the PG in the aqueous dispersion can be degraded by the action of the peptidoglycan degrading enzyme. As a result, the stability of the crosslinked resin particles in the aqueous dispersion is reduced, and the crosslinked resin particles can coagulate with each other. That is, by performing the mixing step, an aggregate of the crosslinked resin particles can be obtained.

[0120] The peptidoglycan decomposition enzyme is not particularly limited as long as it is an enzyme that can decompose peptidoglycan. Examples of the peptidoglycan decomposition enzyme include lysozyme, labia, β-N-acetylglucosaminidase, endolysin, autolysin, etc. Among these, lysozyme is preferred from the viewpoint of economical advantage. These peptidoglycan decomposition enzymes may be used alone or in combination of two or more.

[0121] As the peptidoglycan degrading enzyme, commercially available products can also be used, such as "lysozyme" and "achromopeptidase" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0122] In the present production method (e.g., mixing step), the amount of the peptidoglycan decomposition enzyme used is not particularly limited. The amount of the peptidoglycan decomposition enzyme used in the present production method (e.g., mixing step) is preferably 0.05 to 5 parts by weight, more preferably 0.1 to 4 parts by weight, even more preferably 0.2 to 3 parts by weight, and particularly preferably 0.3 to 2 parts by weight, relative to 100 parts by weight of the resin particles. When the amount of the peptidoglycan decomposition enzyme used is 0.05 parts by weight or more relative to 100 parts by weight of the resin particles, there is an advantage that the degree of decomposition of PG is increased and the coagulation property is improved. When the amount of the peptidoglycan decomposition enzyme used is 5 parts by weight or less relative to 100 parts by weight of the resin particles, there is an advantage that no excess enzyme remains, and there is no adverse effect such as a decrease in heat resistance during melt kneading.

[0123] In the mixing step, it is preferable to stir the mixture obtained by mixing the aqueous dispersion and the peptidoglycan degrading enzyme. The stirring speed of the mixture is not particularly limited and may be appropriately set depending on the type of stirrer and / or the amount of the treatment liquid. The stirring speed of the mixture is, for example, preferably 1 rpm to 3000 rpm, more preferably 10 rpm to 2000 rpm, further preferably 20 rpm to 1500 rpm, and particularly preferably 40 rpm to 1000 rpm. This configuration has the advantage that the peptidoglycan degrading enzyme acts uniformly, and as a result, PG is easily degraded.

[0124] In the mixing step, the temperature of the mixture obtained by mixing the aqueous dispersion with the peptidoglycan degrading enzyme is preferably kept within a certain range. The temperature of the mixture is, for example, preferably 0° C. to 70° C., more preferably 5° C. to 60° C., further preferably 10° C. to 55° C., and particularly preferably 15° C. to 50° C. This temperature range has the advantage that PG is easily decomposed.

[0125] In the mixing step, the pH of the mixture obtained by mixing the aqueous dispersion with the peptidoglycan degrading enzyme is preferably set within a certain range. The pH of the mixture is, for example, preferably 3.0 to 11.5, more preferably 3.3 to 10.5, and even more preferably 3.5 to 9.5. This pH range has the advantage that PG is easily decomposed.

[0126] In the mixing step, the peptidoglycan degrading enzyme may be added all at once, continuously, or in portions.

[0127] <Drying process> In the drying step, the coagulated product obtained in the mixing step is dried to obtain a powder containing crosslinked resin particles.

[0128] In the drying step, (i) the aqueous dispersion containing the coagulated material obtained in the mixing step may be dried as it is using a dryer or the like, or (ii) the aqueous dispersion containing the coagulated material obtained in the mixing step may be separated from the aqueous dispersion containing the coagulated material, and the separated coagulated material may be dried using a dryer or the like. Examples of methods for separating the coagulated material from the aqueous dispersion include filtration and centrifugation. Examples of methods for drying the separated coagulated material include heat drying using a dryer (oven) and freeze drying.

[0129] A case where heat drying is adopted in the drying step will be described. In this case, the heating temperature in the drying step is not particularly limited. Since the drying efficiency can be increased while preventing deterioration of the resin particles, the heating temperature is preferably 40°C to 100°C, more preferably 45°C to 95°C, even more preferably 50°C to 90°C, and particularly preferably 55°C to 80°C. In the drying step, the time for which the coagulated material is held at the above-mentioned heating temperature (sometimes referred to as heating time or drying time) is not particularly limited. Since the moisture content can be reduced while preventing deterioration of the resin particles, the time for which the coagulated material is held at the heating temperature is preferably 5 minutes to 50 hours, more preferably 10 minutes to 45 hours, even more preferably 20 minutes to 40 hours, and particularly preferably 30 minutes to 30 hours.

[0130] <Physical properties of crosslinked resin particles> Various physical properties of the crosslinked resin particles obtained through the crosslinking step, that is, the crosslinked resin particles contained in the present powder and granule, will be described below.

[0131] (Gel fraction) The present crosslinked resin particles may have a crosslinked structure in which molecular chains of PHA are bonded to each other. The amount of crosslinked structures in the crosslinked resin particles affects the gel fraction of the crosslinked resin particles, and specifically, the more crosslinked structures there are, the higher the gel fraction. The present crosslinked resin particles have a certain amount or more of crosslinked structures, and therefore exhibit a high gel fraction, specifically, a gel fraction of 50% or more. Since the present crosslinked resin particles have a gel fraction of 50% or more, the crosslinked resin particles have excellent hardness, heat resistance, and solvent resistance.

[0132] The value of the gel fraction is preferably 60% or more, more preferably 70% or more, even more preferably 75% or more, and particularly preferably 80% or more. It may also be 85% or more, or 90% or more. The upper limit of the gel fraction is not particularly limited, and may be 100% or less. From the viewpoint of production efficiency of crosslinked resin particles, the upper limit of the gel fraction is preferably 99.5% or less, more preferably 99% or less. The upper limit of the gel fraction may also be 98% or less, 97% or less, or 96% or less.

[0133] The gel fraction is a value measured as follows: (1) A dried product of crosslinked resin particles is added to chloroform so as to give a concentration of 0.7% by weight, and the resulting mixture is kept at 60°C for 30 minutes to obtain a chloroform solution; (2) After that, the chloroform solution is allowed to stand at room temperature for 3 hours, and then the chloroform solution is filtered through a membrane filter having a pore size of 0.45 μm; (3) The gel remaining on the filter is dried, and the weight of the dried gel together with the filter is measured, and the gel fraction is calculated using the following formula. Formula: gel fraction (%)={(weight of filter including dried gel−weight of filter only) / weight of dried crosslinked resin particles used in measurement}×100.

[0134] (Volume average particle size) The crosslinked resin particles preferably have a volume average particle diameter of 0.10 μm to 10.00 μm. This configuration allows the crosslinked resin particles to be suitably used in various applications as described below. From the viewpoint of practical use opportunities, the lower limit of the volume average particle diameter is more preferably 0.15 μm or more, and even more preferably 0.20 μm or more. Moreover, from the viewpoint of productivity (production of biodegradable resin (A) and / or crosslinking treatment, etc.), the upper limit of the volume average particle diameter is more preferably 8.00 μm or less, and even more preferably 5.00 μm or less.

[0135] In this specification, the volume average particle diameter (MV) of the crosslinked resin particles is a value obtained by measuring an aqueous dispersion liquid in which the crosslinked resin particles are dispersed in an aqueous medium. More specifically, the volume average particle diameter (MV) of the crosslinked resin particles is a value calculated by the following formula (1), i.e., formula (2), when the particle diameters of the individual crosslinked resin particles contained in a group of k total crosslinked resin particles are d1, d2,...di...dk in ascending order, and the volumes of the individual crosslinked resin particles are V1, V2,...Vi...Vk (here, the volume of the crosslinked resin particles with particle diameter di is Vi).

[0136]

number

[0137] In addition, a general-purpose measuring device can be used as a device for measuring the particle size and volume of the crosslinked resin particles in the aqueous dispersion, and an example of such a device is MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. In addition, in this specification, the volume average particle size of the uncrosslinked resin particles can be measured by replacing "crosslinked resin particles" with "uncrosslinked resin particles" in the above method.

[0138] (Apparent density) When the crosslinked resin particles are not expanded, the apparent density of the crosslinked resin particles is relatively large. The apparent density of the crosslinked resin particles is 0.6 g / cm. 3 It is preferable that the density exceeds 0.7 g / cm 3 More preferably, it is 0.9 g / cm or more. 3 The apparent density of the crosslinked resin particles can be determined by the method described in JIS K0061 (Method for measuring density and specific gravity of chemical products) or JIS Z8807 (Method for measuring density and specific gravity of solids).

[0139] (grain weight) The average weight per particle of the present crosslinked resin particles is not particularly limited. For example, when the volume average particle size of the present crosslinked resin particles is 10.0 μm or less, the average weight per particle of the crosslinked resin particles can be much less than 0.1 mg.

[0140] <Physical properties of powders> The powder obtained by the above-mentioned production method can be said to be the following powder: A powder or granule comprising crosslinked resin particles, the crosslinked resin particles comprising a polyhydroxyalkanoate resin and a peptidoglycan decomposing enzyme, the gel fraction being 50% or more, and the volume average particle diameter being 0.10 μm to 10.00 μm.

[0141] The content of the crosslinked resin particles in the powder obtained by the present production method (i.e., the present powder) is not particularly limited. The content of the crosslinked resin particles in the present powder is preferably 30% by weight to 100% by weight, more preferably 35% by weight to 99.9% by weight, even more preferably 40% by weight to 99.9% by weight, and particularly preferably 45% by weight to 99.9% by weight, in 100% by weight of the powder. When the content of the crosslinked resin particles is 30% by weight to 100% by weight, the ratio of the crosslinked resin particles in the powder is increased, which is advantageous in that the productivity is improved.

[0142] (Median diameter) The median diameter of the powder is not particularly limited. The median diameter of the powder is preferably 20 μm to 10 mm, more preferably 25 μm to 7 mm, further preferably 30 μm to 5 mm, and particularly preferably 35 μm to 3 mm. When the median diameter of the powder is 20 μm to 10 mm, the powder is advantageously easy to handle when weighing.

[0143] The median diameter of the powder or granule is a value obtained by measuring using a dispersion liquid in which the powder or granule is dispersed in an aqueous solvent. A general-purpose measuring device can be used as the measuring device, and an example of such a device is MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. More specifically, the particle diameter at which the larger side and the smaller side are equal (50%) in the cumulative distribution of particle diameters obtained by measurement is defined as the "median diameter (D50)". When powder or granules tend to aggregate in an aqueous solvent, it is preferable to add the powder or granules to an aqueous solvent to which a small amount of the above-mentioned dispersant has been added, stir the mixture, and measure the powder or granules in a state where they are not aggregated.

[0144] (moisture content) The moisture content of the powder is not particularly limited. The moisture content of the powder is preferably 0% to 1.5%, more preferably 0% to 1%, further preferably 0% to 0.8%, and particularly preferably 0% to 0.6%. When the moisture content of the powder is 0% to 1.5%, there is an advantage that deterioration of the resin during melt kneading can be prevented.

[0145] <Applications of powder and granular materials> The use of the powder or granule obtained by the present production method (i.e., the present powder or granule) is not particularly limited, and it can be used in applications where conventionally known crosslinked resin particles are used.Specific examples include resin modifiers, rheology adjusters for paints or adhesives, paint pigments, paper coating agents, matting agents, antiblocking agents, cosmetic additives, toner additives, spacers for liquid crystals, coating agents, fillers for adhesive tapes, fiber processing agents, medical diagnostic test particles, fillers, aqueous coating films, coated paper, resin tubes, foamed particles, packaging materials, containers, cosmetic containers, antifouling resin compositions, heat seal paper, handle moldings, forks, films, resin films for twist packaging materials, bags, gloves, binding materials, multilayer films, stretched films, fibers, multifilaments, meltblown nonwoven fabrics, masks, pile fabrics, coffee filters, inflation moldings, blow moldings, calendar sheet moldings, injection moldings, laminates, films, sheets, etc.The uses of the present powder or granule are not limited to these.

[0146] [3. Method for producing thermoplastic resin composition] A method for producing a thermoplastic resin composition according to one embodiment of the present invention includes a mixing step of mixing parts by weight of a thermoplastic resin with a powder or granule produced by the method for producing a powder or granule described in the section [2. Method for producing a powder or granule].

[0147] The thermoplastic resin composition obtained by the method for producing a thermoplastic resin composition according to one embodiment of the present invention can also be said to be a thermoplastic resin composition according to one embodiment of the present invention. In this specification, the "thermoplastic resin composition according to one embodiment of the present invention" may be referred to as the "present resin composition".

[0148] In a preferred embodiment of the present invention, the resin composition can provide a molded article having excellent tensile impact strength.

[0149] A molded article can be obtained by molding the thermoplastic resin composition by a known method.

[0150] In the method for producing a thermoplastic resin composition according to one embodiment of the present invention, the preferred numerical range of the amount of powder or granules to be mixed with the thermoplastic resin depends on the amount of crosslinked resin particles contained in the powder or granules. The amount of powder or granules to be used is preferably such that the content of the crosslinked resin particles in the resulting thermoplastic resin composition is 0.1 parts by weight or more, 0.3 parts by weight or more, 0.5 parts by weight or more, 1 part by weight or more, 3 parts by weight or more, 5 parts by weight or more, 7 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more per 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles. The amount of powder or granule used is preferably such that the content of crosslinked resin particles in the resulting thermoplastic resin composition is 60 parts by weight or less, 55 parts by weight or less, 53 parts by weight or less, 50 parts by weight or less, 45 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 12 parts by weight or less, or 10 parts by weight or less, per 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles.

[0151] In the method for producing a thermoplastic resin composition according to one embodiment of the present invention, the preferred range of the amount of the thermoplastic resin to be mixed with the powder or granule depends on the amount of the crosslinked resin particles contained in the powder or granule. The amount of the thermoplastic resin to be used is preferably such that the content of the thermoplastic resin in the resulting thermoplastic resin composition is 40 parts by weight or more, 45 parts by weight or more, 47 parts by weight or more, 50 parts by weight or more, 55 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 88 parts by weight or more, or 90 parts by weight or more per 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles. The amount of thermoplastic resin used is preferably such that the content of thermoplastic resin in the resulting thermoplastic resin composition is 99.9 parts by weight or less, 99.7 parts by weight or less, 99.5 parts by weight or less, 99 parts by weight or less, 97 parts by weight or less, 95 parts by weight or less, 93 parts by weight or less, 90 parts by weight or less, 85 parts by weight or less, 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less, per 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles.

[0152] Here, a case where a coagulation aid is used in the method for producing powder or granular material, and the coagulation aid is a thermoplastic resin, will be described. In this case, the thermoplastic resin used as the coagulation aid cannot be distinguished from the thermoplastic resin in the thermoplastic resin composition. Therefore, in this case, the "thermoplastic resin in the thermoplastic resin composition" also includes the thermoplastic resin used as the coagulation aid. In other words, the content of the thermoplastic resin in the obtained thermoplastic resin composition also includes the amount of the thermoplastic resin used as the coagulation aid.

[0153] Specific embodiments of the thermoplastic resin are the same as those described above, and therefore the description is incorporated herein by reference and will not be described here.

[0154] As the thermoplastic resin in the resin composition, a polyester resin is particularly preferred. Specific embodiments of the polyester resin are the same as those described above, and therefore the description is incorporated herein by reference and will not be repeated here.

[0155] Since the powder (crosslinked resin particles) contains a biodegradable PHA, it is preferable that the thermoplastic resin in the resin composition also contains a biodegradable resin, i.e., a biodegradable resin. This configuration has the advantage that the biodegradability of the entire thermoplastic resin composition and the entire molded product of the thermoplastic resin composition can be improved.

[0156] The biodegradable resin contained in the thermoplastic resin may be a biodegradable resin having a glass transition temperature of less than 0°C, may be a biodegradable resin having a glass transition temperature of 0°C or higher, or may be a mixture of a biodegradable resin having a glass transition temperature of less than 0°C and a biodegradable resin having a glass transition temperature of 0°C or higher. Since the effects of blending powder particles (crosslinked resin particles) (for example, the effect of improving impact resistance) can be enjoyed more, the biodegradable resin contained in the thermoplastic resin preferably contains a biodegradable resin having a glass transition temperature of 0°C or higher. The biodegradable resin contained in the thermoplastic resin preferably contains 50% by weight or more of a biodegradable resin having a glass transition temperature of 0°C or higher, more preferably contains 60% by weight or more, even more preferably contains 70% by weight or more, and particularly preferably contains 80% by weight or more, of the biodegradable resin 100% by weight. The biodegradable resin may be composed only of a biodegradable resin having a glass transition temperature of 0°C or higher.

[0157] Furthermore, when the powder or granule (crosslinked resin particles) contains a resin produced from a raw material derived from plants, from the viewpoint of resource circulation, it is preferable that the thermoplastic resin in the resin composition also contains a resin produced from a raw material derived from plants, and it is more preferable that the thermoplastic resin is composed only of a resin produced from a raw material derived from plants.

[0158] The case where the thermoplastic resin in the present resin composition contains a biodegradable resin will be described. The thermoplastic resin in the present resin composition preferably contains 10% by weight to 100% by weight of the biodegradable resin in 100% by weight of the thermoplastic resin. The thermoplastic resin in the present resin composition more preferably contains 30% by weight or more of the biodegradable resin in 100% by weight of the thermoplastic resin, more preferably contains 50% by weight or more, even more preferably contains 70% by weight or more, and particularly preferably contains 90% by weight or more. The thermoplastic resin in the present resin composition may be composed of only the biodegradable resin.

[0159] Since the thermoplastic resin composition and its molded body can enjoy the impact resistance improving effect of the powder (crosslinked resin particles), the biodegradable resin contained in the thermoplastic resin in the resin composition preferably contains a polyester resin, more preferably contains an aliphatic polyester, and particularly preferably contains PHA and / or polylactic acid. The PHA used as the thermoplastic resin in the resin composition preferably has a gel fraction of less than 50%. The PHA used as the thermoplastic resin in the resin composition preferably does not have a crosslinked structure.

[0160] The case where the thermoplastic resin in the present resin composition contains PHA and / or polylactic acid as a biodegradable resin will be described below. The thermoplastic resin in the present resin composition preferably contains 10% by weight to 100% by weight of PHA and polylactic acid in total, more preferably 30% by weight or more, even more preferably 50% by weight or more, even more preferably 70% by weight or more, and particularly preferably 90% by weight or more, based on 100% by weight of the thermoplastic resin.

[0161] The PHA usable as the thermoplastic resin in the present resin composition is not particularly limited, and examples thereof include polyglycolic acid, P3HA, poly(4-hydroxyalkanoate) resins, etc. As the PHA, only one type may be used, or two or more types may be used in combination. As the PHA used as the thermoplastic resin in the present resin composition, P3HA is particularly preferred.

[0162] The case where the crosslinked resin particles contain P3HA and the thermoplastic resin in the present resin composition contains P3HA will be described. The P3HA that can be used as the thermoplastic resin in the present resin composition is the same as the P3HA related to the crosslinked resin particles, and the above-mentioned various P3HAs can be used. The P3HA contained in the thermoplastic resin in the present resin composition may be a resin having the same composition as the P3HA contained in the crosslinked resin particles, or may be a resin having a different composition and / or physical properties. The P3HA contained in the thermoplastic resin in the present resin composition is preferably a resin having a different composition and / or physical properties from the P3HA contained in the crosslinked resin particles, and is more preferably a resin harder than the P3HA contained in the crosslinked resin particles.

[0163] The case where the P3HA used as the thermoplastic resin in the resin composition contains 3-hydroxybutanoic acid (3HB) repeating units will be described. In this case, from the viewpoint of the balance between flexibility and strength, the composition ratio of the 3HB repeating units in the total monomer repeating units of P3HA (100 mol%) is preferably 80 mol% to 99 mol%, more preferably 82 mol% to 97 mol%. When the composition ratio of the 3HB repeating units in P3HA is 80 mol% or more, the rigidity of P3HA can be further improved. On the other hand, when the composition ratio of the 3HB repeating units in P3HA is 99 mol% or less, the flexibility of P3HA tends to be further improved. As P3HA, two or more types having different composition ratios of the 3HB repeating units may be used in combination.

[0164] The weight average molecular weight of the PHA used as the thermoplastic resin in the present resin composition is not particularly limited, but is preferably 50,000 to 3,000,000, more preferably 100,000 to 2,000,000, and even more preferably 150,000 to 1,500,000. When the weight average molecular weight of the PHA is 50,000 or more, sufficient rigidity and / or strength can be obtained in the present resin composition and its molded article. On the other hand, a PHA having a weight average molecular weight of 3,000,000 or less may have the advantage that the PHA is easy to manufacture and / or easy to handle in order to achieve the object of one embodiment of the present invention.

[0165] Regarding the PHA and polylactic acid used as the thermoplastic resin, other aspects than those described above are the same as those explained in the section [2. Crosslinked resin particles] above, so that the explanation therein is incorporated by reference and will not be repeated here.

[0166] <Nucleating agent> In the mixing step, in addition to the thermoplastic resin and the crosslinked resin particles, a crystal nucleating agent may be further mixed. In other words, the present resin composition may further contain a crystal nucleating agent. When the thermoplastic resin composition contains a crystal nucleating agent, in the case where the thermoplastic resin is a crystalline resin, crystallization during molding is promoted, and molding processability, productivity, etc. can be improved. When the present resin composition contains a crystal nucleating agent, it also has the advantage that a thermoplastic resin composition and a molded article thereof having excellent heat resistance or mechanical properties can be obtained.

[0167] The crystal nucleating agent is not particularly limited, and conventionally known ones can be used. The crystal nucleating agent can be, for example, inorganic substances such as talc, kaolinite, montmorillonite, mica, synthetic mica, clay, zeolite, silica, carbon black, graphite, boron nitride, zinc oxide, titanium oxide, tin oxide, calcium carbonate, magnesium carbonate, aluminum oxide, neodymium oxide, barium sulfate, sodium chloride, and metal phosphate; sugar alcohol compounds derived from natural products such as erythritol, pentaerythritol, galactitol, mannitol, and arabitol; polysaccharides such as chitin and chitosan; polyols such as aliphatic alcohols (polyols), polyvinyl alcohol, and polyethylene oxide; sodium benzoate, potassium benzoate, lithium benzoate, calcium benzoate, magnesium benzoate, barium benzoate, lithium terephthalate, sodium terephthalate, and terephthalic acid salts. metal salts of organic carboxylic acids such as potassium phosphate, calcium oxalate, sodium laurate, potassium laurate, sodium myristate, potassium myristate, calcium myristate, sodium octacosanoate, calcium octacosanoate, sodium stearate, potassium stearate, lithium stearate, calcium stearate, magnesium stearate, barium stearate, sodium montanate, calcium montanate, sodium toluate, sodium salicylate, potassium salicylate, zinc salicylate, aluminum dibenzoate, potassium dibenzoate, lithium dibenzoate, sodium β-naphthalate, and sodium cyclohexanecarboxylate; organic sulfonates such as sodium p-toluenesulfonate and sodium sulfoisophthalate;Carboxylic acid amides such as ethylene stearic acid amide, ethylene bislauric acid amide, palmitic acid amide, hydroxystearic acid amide, erucic acid amide, and trimesic acid tris(t-butylamide), lauric acid esters, palmitic acid esters, oleic acid esters, stearic acid esters, erucic acid esters, N-oleyl palmitic acid ester, N-oleyl oleic acid ester, N-oleyl stearate ester, N-stearyl oleic acid ester, N-stearyl stearate ester, N-stearyl erucic acid ester, methylene bisstearate ester, ethylene bislauric acid ester, ethylene biscapric acid ester, ethylene bisoleic acid ester, ethylene bisstearic acid ester, ethylene biserucic acid ester, ethylene Examples of the nucleating agent include carboxylic acid esters such as butylene bisisostearate, butylene bisstearate, and p-xylylene bisstearate; dicarboxylic acid derivatives such as dimethyl adipate, dibutyl adipate, diisodecyl adipate, and dibutyl sebacate; cyclic compounds having a functional group C=O and one or more functional groups selected from the group consisting of NH, S, and O in the molecule, such as indigo, quinacridone, and quinacridone magenta; sorbitol derivatives such as bisbenzylidene sorbitol and bis(p-methylbenzylidene) sorbitol; compounds containing a nitrogen-containing heteroaromatic nucleus such as pyridine, triazine, and imidazole; phosphoric acid ester compounds, bisamides of higher fatty acids, and metal salts of higher fatty acids; branched polylactic acid; and low molecular weight poly(3-hydroxybutyrate). These crystal nucleating agents may be used alone or in combination of two or more.

[0168] The amount of the crystal nucleating agent used in the mixing step is not particularly limited as long as it can promote the crystallization of the thermoplastic resin. The amount of the crystal nucleating agent used is preferably 0.05 parts by weight to 12.00 parts by weight, more preferably 0.10 parts by weight to 10.00 parts by weight, and even more preferably 0.50 parts by weight to 8.00 parts by weight, relative to 100 parts by weight of the thermoplastic resin. When the amount of the crystal nucleating agent used is within the above range, the effect of the crystal nucleating agent can be obtained while suppressing the decrease in viscosity during molding and the physical properties of the molded product.

[0169] <Lubricant> In the mixing step, in addition to the thermoplastic resin and the crosslinked resin particles, a lubricant may be further mixed. In other words, the resin composition may further contain a lubricant. When the thermoplastic resin composition contains a lubricant, the surface smoothness of the obtained molded body can be improved. The lubricant is not particularly limited. Examples of the lubricant include, but are not limited to, fatty acid metal salts such as magnesium stearate and calcium stearate; fatty acid amides such as behenic acid amide, stearic acid amide, erucic acid amide, oleic acid amide, methylene bisstearic acid amide, and ethylene bisstearic acid amide; polyethylene wax, oxidized polyester wax, glycerin mono fatty acid esters such as glycerin monostearate, glycerin monobehenate, and glycerin monolaurate; organic acid monoglycerides such as succinic acid saturated fatty acid monoglycerides; sorbitan fatty acid esters such as sorbitan behenate, sorbitan stearate, and sorbitan laurate; polyglycerin fatty acid esters such as diglycerin stearate, diglycerin laurate, tetraglycerin stearate, tetraglycerin laurate, decaglycerin stearate, and decaglycerin laurate; and higher alcohol fatty acid esters such as stearyl stearate. The lubricant may be used alone or in combination of two or more.

[0170] The amount of lubricant used in the mixing step (when multiple lubricants are used, the total amount used) is not particularly limited as long as it can impart lubricity to the molded body. The amount of the lubricant used is preferably 0.01 to 20.00 parts by weight, more preferably 0.05 to 10.00 parts by weight, even more preferably 0.10 to 10.00 parts by weight, even more preferably 0.20 to 5.00 parts by weight, and particularly preferably 0.30 to 4.00 parts by weight, relative to 100 parts by weight of the thermoplastic resin. When the amount of the lubricant used is within the above range, it is possible to obtain the effect of the lubricant while avoiding bleeding out of the lubricant onto the surface of the molded body.

[0171] <Other ingredients> In the mixing step, in addition to the thermoplastic resin, powder, and granules, and the crystal nucleating agent and lubricant that are optionally used, other components such as plasticizers, organic fillers, inorganic fillers, antioxidants, hydrolysis inhibitors, ultraviolet absorbers, colorants such as dyes and pigments, and antistatic agents may be mixed within the range that does not impair the functions of the obtained molded body.

[0172] The plasticizer is not particularly limited. Examples of the plasticizer include polyester-based plasticizers such as polypropylene glycol sebacate ester, aliphatic dibasic acid ester-based plasticizers such as di-1-butyl adipate, di-n-butyl sebacate, and di-2-ethylhexyl azelate, glycerin-based plasticizers such as glycerin diacetomonolaurate, glycerin diacetomonocaprylate, and glycerin diacetomonodecanoate, polycarboxylic acid ester-based plasticizers such as tri-2-ethylhexyl acetyl citrate and tributyl acetyl citrate, and polyamide-based plasticizers such as polyethylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) block and / or random copolymers, and polytetramethylene glycol. Examples of the plasticizer include alkylene glycol-based plasticizers, phosphoric acid ester-based plasticizers such as diphenyl-2-ethylhexyl phosphate and diphenyloctyl phosphate, epoxy-based plasticizers such as epoxidized soybean oil and epoxidized linseed oil fatty acid butyl ester, and castor oil-based plasticizers such as castor oil fatty acid esters, methyl ricinoleate, ethyl ricinoleate, isopropyl ricinoleate, butyl ricinoleate, ethylene glycol monoricylate, propylene glycol monoricylate, trimethylolpropane monoricylate, sorbitan monoricylate, castor oil fatty acid polyethylene glycol ester, castor oil ethylene oxide adduct, castor oil-based polyol, castor oil-based toluol, and castor oil-based diol. These plasticizers may be used alone or in combination of two or more.

[0173] The organic filler is not particularly limited. Examples of the organic filler include fillers made of naturally derived materials such as wood-based materials (e.g., wood chips, wood flour, sawdust, etc.), rice husks, rice flour, starch, corn starch, rice straw, wheat straw, and natural rubber; organic fibers such as natural vegetable fibers, natural animal fibers, and synthetic fibers; and fillers made of synthetic resin materials such as polyester, polyacrylic, polyamide, nylon, polyethylene, polyolefin, polyvinyl alcohol, polyvinyl chloride, polyurethane, polyacetal, aramid, PBO (poly-p-phenylene benzobisoxazole), polyphenylene sulfide, acetyl cellulose, polybenzazole, polyarylate, polyvinyl acetate, and synthetic rubber.

[0174] The plant-derived natural fibers are not particularly limited. Examples of the plant-derived natural fibers include kenaf fiber, abaca fiber, bamboo fiber, jute fiber, hemp fiber, linen fiber, henequen (sisal), ramie fiber, hemp, cotton, banana fiber, coconut fiber, palm, paper mulberry, mitsumata, bagasse, etc. In addition, regenerated fibers such as pulp, cellulose fiber, and rayon processed from plant fibers are also included. Examples of the animal-derived natural fibers include wool, silk, cashmere, and mohair.

[0175] The inorganic filler is not particularly limited. Examples of the inorganic filler include silica-based inorganic fillers (e.g., quartz, fumed silica, silicic anhydride, fused silica, crystalline silica, amorphous silica, fillers obtained by condensing alkoxysilanes, ultrafine amorphous silica, etc.), alumina, zircon, iron oxide, zinc oxide, titanium oxide, silicon nitride, boron nitride, aluminum nitride, silicon carbide, glass, silicone rubber, silicone resin, titanium oxide, carbon fiber, mica, graphite, carbon black, ferrite, graphite, diatomaceous earth, white clay, clay, talc, calcium carbonate, manganese carbonate, magnesium carbonate, barium sulfate, silver powder, etc. These inorganic fillers may be surface-treated to increase dispersibility in the resin composition. In addition, these inorganic fillers may be used alone or in combination of two or more.

[0176] The antioxidant is not particularly limited. Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. These antioxidants may be used alone or in combination of two or more.

[0177] The hydrolysis inhibitor is not particularly limited. Examples of the hydrolysis inhibitor include carbodiimide compounds, epoxy compounds, isocyanate compounds, and oxazoline compounds. These hydrolysis inhibitors may be used alone or in combination of two or more.

[0178] The ultraviolet absorbing agent is not particularly limited. Examples of the ultraviolet absorbing agent include benzophenone compounds, benzotriazole compounds, triazine compounds, salicylic acid compounds, cyanoacrylate compounds, and nickel complex compounds. These ultraviolet absorbing agents may be used alone or in combination of two or more.

[0179] The coloring agent such as the pigment or dye is not particularly limited. Examples of the coloring agent include inorganic coloring agents such as titanium oxide, calcium carbonate, chromium oxide, cuprous oxide, calcium silicate, iron oxide, carbon black, graphite, titanium yellow, and cobalt blue; soluble azo pigments such as lake red, lithol red, and brilliant carmine; insoluble azo pigments such as dinitrile orange and fast yellow; phthalocyanine pigments such as monochlorophthalocyanine blue, polychlorophthalocyanine blue, and polybromophthalocyanine green; condensed polycyclic pigments such as indigo blue, perylene red, isoindolinone yellow, and quinacridone red; and dyes such as oracet yellow. These coloring agents may be used alone or in combination of two or more.

[0180] The antistatic agent is not particularly limited. Examples of the antistatic agent include low molecular weight antistatic agents such as fatty acid ester compounds, aliphatic ethanolamine compounds, and aliphatic ethanolamide compounds, and polymeric antistatic agents. These antistatic agents may be used alone or in combination of two or more.

[0181] In the mixing step, in addition to the thermoplastic resin and powder, as well as the optionally used crystal nucleating agent, lubricant, and other components described above, the following components may be further mixed: catalyst deactivators (hindered phenol compounds, thioether compounds, vitamin compounds, triazole compounds, polyamine compounds, hydrazine derivative compounds, phosphorus compounds, etc.), release agents (montanic acid and its salts, its esters, its half esters, stearyl alcohol, stearamide, polyethylene wax, etc.), color inhibitors (phosphites, hypophosphites, etc.), silane coupling agents (epoxy silane coupling agents, amino silane coupling agents, (meth)acrylic silane coupling agents, isocyanate silane coupling agents, etc.), flame retardants (red phosphorus, Phosphate esters, brominated polystyrene, brominated polyphenylene ether, brominated polycarbonate, aluminum hydroxide, magnesium hydroxide, melamine and cyanuric acid or its salts, silicon compounds, etc.), conductive agents (carbon black, etc.), sliding improvers (graphite, fluororesin, etc.), epoxy compounds (glycidyl ether compounds, glycidyl ester compounds, polymer compounds grafted or copolymerized with glycidyl compounds, etc.), acid anhydride compounds (maleic anhydride, succinic anhydride, polymer compounds grafted or copolymerized with acid anhydride, etc.), carbodiimide compounds (N,N'-di-2,6-diisopropylphenylcarbodiimide, 2,6,2',6'-tetraisopropyldiphenylcarbodiimide, polycarbodiimide, etc.), etc.

[0182] The amount (content) of each of the other components described above is not particularly limited as long as the effect of one embodiment of the present invention is exhibited, and can be appropriately determined by a person skilled in the art.

[0183] <Mixing process> The method for producing the present resin composition includes a mixing step of mixing the present crosslinked resin particles with a thermoplastic resin.

[0184] The mixing step is not particularly limited as long as it is a method for mixing the present crosslinked resin particles and the thermoplastic resin, and can be performed by a known method. The mixing step can be performed, for example, by a method in which the thermoplastic resin, the crosslinked resin particles, and optionally other components are mixed using an extruder, a kneader, a Banbury mixer, a kneading roll, or the like. The mixing step may include a melt-kneading step in which the present crosslinked resin particles and the thermoplastic resin are melt-kneaded. When melt-kneading, it is preferable to mix them while paying attention to the molecular weight reduction due to thermal decomposition. In addition, the resin composition can also be produced by dissolving each component in a soluble solvent and then removing the solvent.

[0185] When producing a thermoplastic resin composition by melt kneading, each component may be individually charged into an extruder, etc., or each component may be mixed in advance and the resulting mixture may be charged into an extruder, etc. For example, an aqueous dispersion of a thermoplastic resin and an aqueous dispersion of crosslinked resin particles may be mixed, and then the resulting mixture may be dried in a dryer to obtain a mixed powder, and the mixed powder may be charged into an extruder, etc.

[0186] When melt kneading is performed using an extruder, the obtained thermoplastic resin composition may be extruded from the extruder into a strand shape and then cut, thereby processing the thermoplastic resin composition into particle shapes such as a bar shape, a cylinder shape, an elliptical cylinder shape, a sphere shape, a cube shape, a rectangular prism shape, or the like.

[0187] The resin temperature during melt kneading cannot be generally defined because it depends on the melting point, melt viscosity, etc. of the resin used. The resin temperature is preferably 140°C to 250°C, more preferably 150°C to 230°C, and even more preferably 160°C to 210°C, from the viewpoint of uniformly dispersing the crosslinked resin particles in the thermoplastic resin while avoiding thermal decomposition of the thermoplastic resin.

[0188] [4. Manufacturing method of molded body] A method for producing a molded article according to one embodiment of the present invention includes a step of molding a thermoplastic resin composition produced by the method described in the above item [3. Method for producing a thermoplastic resin composition]. That is, in one embodiment of the present invention, a molded article is provided by molding the present resin composition.

[0189] A method for producing a molded body according to another embodiment of the present invention includes a step of molding the powder or granular material produced by the method described in the above section "2. Method for producing powder or granular material". That is, in one embodiment of the present invention, a molded body is provided by molding the powder or granular material.

[0190] The molding method of the thermoplastic resin composition or the powder or granule is not particularly limited, and a commonly used molding method can be applied. Specific examples of the molding method include inflation film molding, extrusion blow molding, injection blow molding, extrusion molding, calendar molding, vacuum molding, injection molding, etc. A molded product obtained by molding a thermoplastic resin composition can also be said to be a molded product containing a thermoplastic resin composition.

[0191] By carrying out the above-mentioned molding method using the present resin composition or the present powder or granule, it is possible to provide a molded product that is excellent in impact resistance and does not cause bleeding out of the plasticizer with good productivity. Specifically, by carrying out the above-mentioned molding method using the present resin composition, it is possible to produce a film molded product, a sheet molded product, a blow molded product, an extrusion molded product, a vacuum molded product, or an injection molded product.

[0192] Molded articles containing the present resin composition or the present powder or granule can be suitably used in agriculture, fisheries, forestry, horticulture, medicine, sanitary products, the food industry, clothing, non-clothing, packaging, automobiles, building materials, and other fields. EXAMPLES

[0193] The following examples are provided to more specifically illustrate one embodiment of the present invention, but the present invention is not limited to these examples.

[0194] [Measurement and evaluation methods] (Weight average molecular weight) The resin to be measured was added to chloroform, and the resulting mixture was heated in a hot water bath at 60°C for 30 minutes. The resulting mixture (chloroform solution) was filtered through a disposable PTFE filter with a 0.45 μm pore size. The filtrate was then subjected to GPC measurement under the following conditions to determine the weight average molecular weight. GPC measurement device: Shimadzu High Performance Liquid Chromatograph 20A System Column: Showa Denko KG 4A (1 column), K-806M (2 columns) Sample concentration: 1mg / ml Free solution: Chloroform solution Free liquid flow rate: 1.0ml / min Sample injection volume: 100 μL Analysis time: 30 minutes Standard sample: standard polystyrene.

[0195] (Volume average particle size of crosslinked resin particles) The volume average particle diameter of the crosslinked resin particles was measured using an aqueous dispersion of crosslinked resin particles or an aqueous dispersion of uncrosslinked resin particles as a sample. A MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. was used as a measuring device. Specifically, the particle diameter and volume of each crosslinked resin particle in the aqueous dispersion of crosslinked resin particles were measured using the above device, and the volume average particle diameter was calculated from the results obtained by the measurement based on the above-mentioned formula (1), i.e., formula (2).

[0196] (Median diameter of powder (D50)) The median diameter of the powder was measured using an aqueous dispersion of the powder as a sample. The measuring device used was a MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. More specifically, the particle diameter at which the larger and smaller sides were equal (50%) in the cumulative particle diameter distribution obtained by the measurement was defined as the "median diameter (D50)".

[0197] (Gel fraction) The dried crosslinked or uncrosslinked resin particles were added to chloroform to a concentration of 0.7% by weight, and the mixture was kept at 60°C for 30 minutes to obtain a chloroform solution. After that, the mixture was left to stand at room temperature for 3 hours, and then the chloroform solution was filtered through a membrane filter with a pore size of 0.45 μm. The inside of the container and the filter were thoroughly washed with chloroform several times while filtering to prevent loss. The gel remaining on the filter was dried, and the weight of the filter was measured, and the gel fraction was calculated using the following formula. Formula: gel fraction=((weight of filter including dry gel−weight of filter only) / weight of crosslinked resin particles or uncrosslinked resin particles used in measurement)×100 (%).

[0198] (Handling evaluation) The powders and granules obtained in each Example and the objects obtained in each Comparative Example were evaluated for handleability according to the following criteria. Grades B (good) and above indicate powders and granules that are easy to handle and have excellent handleability. Grades C (poor) indicate that the powders and granules are creamy and therefore not solidified. A (Excellent): The material is in a powdery or granular form, and both cohesiveness and adhesiveness are very low (very slight). B (Good): The material is in a powdery or granular form and has at least one of cohesiveness and adhesiveness. C (bad): Not granular but creamy.

[0199] Regarding "cohesion," if powders (objects) were observed to stick together when they came into contact with each other and the median diameter of the powders (objects) increased, it was evaluated as having cohesion. Regarding "adhesion," if powders (objects) were observed to adhere to equipment, containers, utensils, etc., it was evaluated as having adhesion.

[0200] (Tensile impact strength) A 500 μm thick molded body (sheet molded body) prepared by the method described below was aged for 7 days under conditions of 23°C and 50% RH, and then punched out into a JIS K 71603 shape to prepare a test specimen. A tensile impact test was performed on the test specimen according to the method in accordance with JIS K 7160 A method.

[0201] [Production of crosslinked resin particles] (raw materials) (1) Uncrosslinked resin particles P3HB3HH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)): Repeating unit composition; (3-hydroxybutyrate) / (3-hydroxyhexanoate)=72 / 28 (mol / mol), weight average molecular weight Mw; 500,000 to 1.5 million The weight average molecular weight of the resin was measured by the method described above. (2) Peroxides Di-sec-butyl peroxydicarbonate: "Lupelox 225" manufactured by Arkema Yoshitomi Co., Ltd., 1-hour half-life temperature: 69°C (3) Polyfunctional compound Triallyl isocyanurate (Manufacturing method) An aqueous dispersion containing crosslinked resin particles was prepared according to the procedure described below.

[0202] <Preparation process> In a glass vessel equipped with a stirrer, a baffle, a nitrogen inlet, a nitrogen outlet, and a thermometer, an aqueous dispersion in which uncrosslinked resin particles are dispersed in water (100 parts by weight in terms of solid content), 200 parts by weight of deionized water, 2 parts by weight of peroxide, 1 part by weight of sodium dioctyl sulfosuccinate, and 0.5 parts by weight of a polyfunctional compound were added to prepare an aqueous dispersion. Then, stirring of the aqueous dispersion obtained was started at room temperature, and the atmosphere in the glass vessel was replaced with nitrogen.

[0203] <Impregnation process> Thereafter, the contents of the glass container (aqueous dispersion) were stirred at room temperature for 1 hour, whereby the peroxide and the polyfunctional compound were impregnated into the interior of the uncrosslinked resin particles.

[0204] <Crosslinking process> Thereafter, the aqueous dispersion was heated to 75°C. After the temperature of the aqueous dispersion reached 75°C, the aqueous dispersion was maintained at 75°C for 3.5 hours. This operation caused the crosslinking agent to react, and an aqueous dispersion in which crosslinked resin particles were dispersed in water was obtained. The solid content concentration in 100% by weight of the aqueous dispersion (approximately the concentration of crosslinked resin particles) was 20% by weight to 25% by weight.

[0205] The volume average particle size and gel fraction of the crosslinked resin particles in the aqueous dispersion were measured by the methods described above. The volume average particle size of the crosslinked resin particles in the aqueous dispersion was 1.7 μm, and the gel fraction was 95%.

[0206] [Production of powder containing crosslinked resin particles] (raw materials) (1) Aqueous dispersion containing crosslinked resin particles The aqueous dispersion obtained in the above [Production of crosslinked resin particles] (2) Coagulation aid Aqueous dispersion of P3HB3HH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)) resin particles: solids concentration: 50% by weight, volume average particle size of resin particles in the aqueous dispersion: 2 μm to 3 μm P3HB3HH (Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)) powder Pentaerythritol: NeuRizer P manufactured by Nippon Synthetic Chemical Industry Co., Ltd. Behenic acid amide: BNT22H manufactured by Nippon Fine Chemicals Here, the P3HB3HH used as the coagulation aid was Kaneka Biodegradable Polymer PHBH (registered trademark) manufactured by Kaneka Corp. The repeating unit composition of the P3HB3HH was (3-hydroxybutyrate) / (3-hydroxyhexanoate)=94.4 / 5.6 (mol / mol), and the weight average molecular weight was 530,000. (3) Peptidoglycan-degrading enzymes Lysozyme, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0207] (Manufacturing method) The method for producing the powder or granules in each example (that is, the mixing step and the drying step) will be described below.

[0208] <Example 1> While stirring the aqueous dispersion of crosslinked resin particles, 1 part by weight of a peptidoglycan-degrading enzyme (lysozyme) was added per 100 parts by weight of the solids in the aqueous dispersion (i.e., the crosslinked resin particles), causing the crosslinked resin particles to coagulate, thereby obtaining a coagulated crosslinked resin particle mixture (mixing process).

[0209] Thereafter, the pH of the aqueous dispersion containing the coagulated material was adjusted. Next, the aqueous dispersion was suction filtered using a filter paper with a retention particle size of 1 μm to recover the coagulated material from the aqueous dispersion. The obtained coagulated material was dried in an oven to obtain a powder of crosslinked resin particles (drying step).

[0210] <Example 2> To the aqueous dispersion of crosslinked resin particles, pentaerythritol and behenic acid amide were added as coagulation aids in the amounts shown in Table 1. Then, while stirring the aqueous dispersion, 0.3 parts by weight of a peptidoglycan decomposition enzyme (lysozyme) was added per 100 parts by weight of the solid content (i.e., crosslinked resin particles) in the aqueous dispersion to coagulate the crosslinked resin particles, thereby obtaining a coagulated product of the crosslinked resin particles (mixing step). Then, a powder of the crosslinked resin particles was obtained in the same manner as in Example 1 (drying step).

[0211] <Examples 3, 4 and 7> To the aqueous dispersion of crosslinked resin particles, an aqueous dispersion of P3HB3HH was added as a coagulation aid in an amount shown in Table 1. Thereafter, while stirring the aqueous dispersion, a peptidoglycan decomposing enzyme (lysozyme) was added in an amount shown in Table 1 per 100 parts by weight of the solid content (i.e., crosslinked resin particles) in the aqueous dispersion, to coagulate the crosslinked resin particles, thereby obtaining a coagulated product of the crosslinked resin particles (mixing step). Thereafter, a powder of the crosslinked resin particles was obtained in the same manner as in Example 1 (drying step).

[0212] <Examples 5, 6 and 9> To the aqueous dispersion of crosslinked resin particles, a powder of P3HB3HH was added as a coagulation aid in an amount shown in Table 1. Thereafter, while stirring the aqueous dispersion, lysozyme was added in an amount shown in Table 1 per 100 parts by weight of the solid content in the aqueous dispersion (i.e., the crosslinked resin particles) to coagulate the crosslinked resin particles, thereby obtaining a coagulated product of the crosslinked resin particles (mixing step). Thereafter, a powder of the crosslinked resin particles was obtained in the same manner as in Example 1 (drying step).

[0213] <Example 8> To the aqueous dispersion of crosslinked resin particles, the aqueous dispersion of P3HB3HH, pentaerythritol, and behenic acid amide were added as coagulation aids in the amounts shown in Table 1. Then, while stirring the aqueous dispersion, 0.3 parts by weight of a peptidoglycan decomposition enzyme (lysozyme) was added per 100 parts by weight of the solid content (i.e., crosslinked resin particles) in the aqueous dispersion to coagulate the crosslinked resin particles, thereby obtaining a coagulated product of the crosslinked resin particles (mixing step). Then, a powder of the crosslinked resin particles was obtained in the same manner as in Example 1 (drying step).

[0214] The coagulation procedure for each comparative example is described below.

[0215] <Comparative Examples 1 and 2> While stirring the aqueous dispersion of crosslinked resin particles, a 20% (wt / wt%) magnesium chloride aqueous solution (Comparative Example 1) or a 20% (wt / wt%) calcium chloride aqueous solution (Comparative Example 2) was added to the aqueous dispersion so that the concentration of magnesium chloride or calcium chloride was 1 part by weight per 100 parts by weight of the solid content (i.e., crosslinked resin particles) in the aqueous dispersion. In the resulting mixture, the crosslinked resin particles became creamy. That is, in Comparative Examples 1 and 2, the crosslinked resin particles did not solidify.

[0216] The median diameter of the powder obtained in each Example was measured to be 30 μm to 3 mm. The moisture content of the powder obtained in each Example was measured to be 0% to 1%. Furthermore, the powder obtained in each Example and the object obtained in each Comparative Example were evaluated for handleability by the above-mentioned method. The results are shown in Table 1.

[0217] It is confirmed from Table 1 that the action of the peptidoglycan degrading enzyme makes it possible to produce powders containing crosslinked resin particles with excellent handleability. It is also seen that in Examples 2 to 9, which contain a coagulation aid, powders containing crosslinked resin particles with even better handleability can be produced.

[0218] [Production of resin composition] (raw materials) (1)Thermoplastic resin P3HB3HH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)): manufactured by Kaneka Corporation, Kaneka Biodegradable Polymer PHBH (registered trademark), repeating unit composition; (3-hydroxybutyrate) / (3-hydroxyhexanoate)=94.4 / 5.6 (mol / mol), weight average molecular weight Mw; 530,000 (2) Crosslinked resin particles Powder containing crosslinked resin particles prepared in Examples 7 and 9 (3) Nucleating Agent Pentaerythritol: NeuRizer P manufactured by Nippon Synthetic Chemical Industry Co., Ltd. (4) Lubricants · Behenic acid amide: BNT22H manufactured by Nippon Fine Chemicals.

[0219] (Manufacturing method) For each Example and Comparative Example, the thermoplastic resin, crosslinked resin particles, crystal nucleating agent and lubricant shown in Table 2 were mixed in the amounts shown in Table 2 to obtain a mixture. The obtained mixture was melt-kneaded for 180 seconds in a twin-screw small kneader (Xplore MC5 manufactured by DSM) with the barrel temperature set to 175°C and the screw rotation speed at 100 rpm to obtain a molten kneaded product (mixture). The obtained molten kneaded product was dried in a dryer at 80°C for 4 hours to sufficiently reduce the moisture content, thereby obtaining a thermoplastic resin composition. Furthermore, the obtained thermoplastic resin composition was press-molded to a predetermined thickness at 165°C to produce a molded product (sheet molded product).

[0220] The tensile impact strength of each of the molded articles (sheet molded articles) of the Examples and Comparative Examples was measured by the method described above. The results are shown in Table 2.

[0221] From Table 2, it is confirmed that the molded products of the examples containing crosslinked resin particles exhibit good tensile impact strength compared to the molded products of the comparative examples in which no crosslinked resin particles are added.

[0222] [Table 1]

[0223] [Table 2] [Industrial Applicability]

[0224] According to one embodiment of the present invention, a method for producing a powder containing biodegradable crosslinked resin particles, which is a novel method for producing a powder having excellent handleability, and the powder can be provided. The powder according to one embodiment of the present invention can provide a thermoplastic resin composition capable of providing a molded product having excellent impact resistance. Therefore, one embodiment of the present invention can be suitably used as a modifier, spacer, antiblocking agent, matting agent, etc. for thermoplastic resins.

Claims

1. A preparation step of preparing an aqueous dispersion containing resin particles containing a polyhydroxyalkanoate-based resin and a peroxide; a crosslinking step of decomposing the peroxide and crosslinking the resin particles; a mixing step of mixing the aqueous dispersion obtained in the crosslinking step with a peptidoglycan decomposition enzyme to obtain a coagulated product containing crosslinked resin particles; A drying step of drying the coagulated material to obtain a powder containing the crosslinked resin particles, The crosslinked resin particles have a gel fraction of 50% or more and a volume average particle diameter of 0.10 μm to 10.00 μm.

2. 2. The method for producing powder or granular material according to claim 1, wherein the mixing step is a step of mixing the aqueous dispersion obtained in the crosslinking step with a peptidoglycan degrading enzyme and further with a coagulation aid to obtain a coagulated product containing the crosslinked resin particles.

3. 3. The method for producing powder or granular material according to claim 2, wherein the amount of the coagulation aid used is 0.1 to 90 parts by weight based on 100 parts by weight of the crosslinked resin particles.

4. 2. The method for producing powder or granular material according to claim 1, wherein the polyhydroxyalkanoate-based resin is a poly(3-hydroxyalkanoate)-based resin.

5. 2. The method for producing powder or granular material according to claim 1, wherein the content of the polyhydroxyalkanoate resin in 100% by weight of the resin particles is 80% by weight or more.

6. 2. The method for producing powder or granular material according to claim 1, wherein the crosslinked resin particles have a gel fraction of 70% to 100%.

7. 2. The method for producing powder or granular material according to claim 1, wherein the amount of the peroxide used is 0.01 to 10 parts by weight based on 100 parts by weight of the resin particles.

8. 2. The method for producing powder or granular material according to claim 1, wherein the preparation step is a step of preparing an aqueous dispersion containing resin particles containing the polyhydroxyalkanoate resin, the peroxide, and a polyfunctional compound.

9. 9. The method for producing powder or granular material according to claim 8, wherein the amount of the polyfunctional compound used is 0.01 to 20 parts by weight based on 100 parts by weight of the resin particles.

10. 2. The method for producing powder or granular material according to claim 1, wherein the preparation step is a step of preparing an aqueous dispersion containing resin particles containing the polyhydroxyalkanoate resin, the peroxide, and a dispersant.

11. The method for producing powder or granular material according to claim 10, wherein the amount of the dispersant used is 0.05 parts by weight to 10 parts by weight based on 100 parts by weight of the resin particles.

12. A method for producing a thermoplastic resin composition, comprising a mixing step of mixing a thermoplastic resin with a powder or granule produced by the method for producing a powder or granule according to any one of claims 1 to 11.

13. A method for producing a molded article, comprising a step of molding a resin composition produced by the method for producing a thermoplastic resin composition according to claim 12.

14. A method for producing a compact, comprising a step of compacting a powder or granular material produced by the method for producing a powder or granular material according to any one of claims 1 to 11.

15. Contains crosslinked resin particles, The crosslinked resin particles are powder particles that contain a polyhydroxyalkanoate resin and a peptidoglycan decomposing enzyme, have a gel fraction of 50% or more, and have a volume average particle diameter of 0.10 μm to 10.00 μm.

Citation Information

Patent Citations

  • Vinylic crosslinked resin particle, its manufacturing method and use thereof

    JP2003082191A

  • Matt acrylic resin film having improved design flexibility after being coated

    JP2009056770A

  • Poly(3-hydroxyalkanoate) resin composition

    WO2019022008A1